Method for manufacturing carrier for electrostatic charge image development, and method for manufacturing electrostatic charge image developer
By controlling the temperature of the resin coated particles and the flow rate in the flow layer, the problem of peeling the resin coated layer in the manufacture of the electrostatic latent image carrier is solved, and the color brightness and quality of the image are improved.
Patent Information
- Application Number
- JP2023117859
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-30
AI Technical Summary
In the prior art, when manufacturing an electrostatic latent image carrier, the resin coating layer is easily peeled off, resulting in darkening of image color and affecting image quality.
By controlling the temperature of the resin-coated particles and the flow rate in the flow layer, ensuring that the resin-coated layer is fixed on the surface of the magnetic particles, avoiding peeling, and using specific stirring conditions and flow layer treatment, including stirring within a specific temperature range and flow rate control in the flow layer.
It effectively suppresses the darkening of image colors and improves image quality.
Smart Images

Figure 2025014913000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for producing a carrier for developing electrostatic images, and a method for producing an electrostatic image developer. [Background technology]
[0002] Patent Document 1 discloses a method for producing a carrier for developing electrostatic images, which includes a coating step in which a coating liquid containing a resin and a solvent and magnetic particles are added to a mixer having stirring blades to form a resin coating layer on the surfaces of the magnetic particles, and the carrier having the resin coating layer is removed from the mixer, and the stirring conditions in the coating step from when the carrier is heated in the mixer to evaporate the solvent and dry it until when the carrier is removed from the mixer satisfy the conditions of the following formulas 1 and 2: 0.2≦the peripheral speed of the stirring blade πDN (m / s)≦2.0 Formula 1 1×10 3 ≦Mixing work load (peripheral speed × mixing time T)≦4×10 3 formula 2 In Equation 1 and Equation 2, D represents the diameter (m) of the stirring blade, N represents the rotation speed (rps) of the stirring blade, and T represents the time (s) from the point at which the load power value of the stirring blade before drying of the solvent increases as the drying progresses and falls to 1.3 times or less the value before drying when the drying is completed, to the point at which stirring in the mixer is completed.
[0003] Patent Document 2 discloses a method for producing an electrophotographic carrier comprising a carrier core material and a resin that coats the surface of the carrier core material, the method being characterized in that the carrier is homogenized using an air classifier. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2022-147738 A [Patent Document 2] Japanese Patent Application Publication No. 8-234499 Summary of the Invention [Problem to be solved by the invention]
[0005] The problem to be solved by the present disclosure is to mix magnetic particles with a mixed liquid containing a resin having a glass transition temperature Tg and a solvent in a mixer, heat the mixture to evaporate the solvent, form a resin coating layer on the surface of the magnetic particles, and obtain resin-coated magnetic particles. A and a fluidized bed device for heating the resin-coated magnetic particles after step A to a temperature T B and a step C of cooling the resin-coated magnetic particles after the step B. A is lower than the glass transition temperature Tg-20°C and step B is not performed, or B The object of the present invention is to provide a method for producing a carrier for developing electrostatic images, which is excellent in suppressing color dullness of the obtained image, as compared with a case where the glass transition temperature is less than the glass transition temperature Tg-20°C or more than the glass transition temperature Tg+50°C. [Means for solving the problem]
[0006] Means for solving the above problems include the following aspects. <1> In a mixer, a mixture containing a resin having a glass transition temperature Tg and a solvent is mixed with magnetic particles, and the mixture is heated to evaporate the solvent to form a resin coating layer on the surface of the magnetic particles to obtain resin-coated magnetic particles. The resin-coated magnetic particles are then heated to a temperature of T A A step A of disintegrating the mixture while maintaining the temperature at 100° C.; In a fluidized bed device, the resin-coated magnetic particles after step A are heated to a temperature T B A step B of flowing the mixture while maintaining the temperature at 100° C.; a step C of cooling the resin-coated magnetic particles after the step B; having The temperature T A and the temperature T Band each of said carriers independently satisfies the glass transition temperature Tg-20°C or higher and the glass transition temperature Tg+50°C or lower.
[0007] <2> In the step A, the resin-coated magnetic particles are mixed at a temperature T A The stirring conditions in the mixer when disintegrating the mixture while maintaining the above condition satisfy the conditions of the following formula 1 and the following formula 2. <1> 2. A method for producing the carrier for developing electrostatic images according to claim 1 . 0.2≦the peripheral speed of the stirring blade πDN (m / s)≦2.0 Formula 1 5×10 2 ≦ Mixing work load (peripheral speed πDN × mixing time T) ≦ 1.5 × 10 3 formula 2 In Equation 1 and Equation 2, D represents the diameter (m) of the stirring blade, N represents the rotation speed (rps) of the stirring blade, and T represents the time (s) from the point at which the load power value of the stirring blade before drying of the solvent increases as the drying progresses and the load power value falls to 1.3 times or less the value before drying when the drying is completed, to the point at which stirring in the mixer is completed. <3> The condition of the formula 2 is the condition of the following formula 2': <2> 2. A method for producing the carrier for developing electrostatic images according to claim 1 . 7×10 2 ≦ Mixing work load (peripheral speed πDN × mixing time T) ≦ 1 × 10 3 formula 2' In equation 2', D represents the diameter (m) of the agitator blade, N represents the rotation speed (rps) of the agitator blade, and T represents the time (s) from the point at which the load power value of the agitator blade before drying of the solvent increases as the drying progresses and the load power value falls to 1.3 times or less the value before drying when drying is completed, to the point at which mixing in the mixer is terminated.
[0008] <4> In the step B, the resin-coated magnetic particles after the step A are heated to a temperature T B and fluidizing the resin-coated magnetic particles for 30 minutes or more while maintaining the temperature at that temperature, and then cooling the temperature Tc of the resin-coated magnetic particles to a glass transition temperature Tg-40°C or lower in the step C. <1> ~ <3> 13. A method for producing the carrier for developing electrostatic images according to claim 12. <5> In the step B, the resin-coated magnetic particles after the step A are heated to a temperature T B The superficial velocity V of the fluidizing gas in the fluidized bed apparatus when the fluidizing gas is fluidized in a state maintained at H (m / s) is between 1 and 5 times the minimum fluidization velocity Umf. <1> ~ <4> 13. A method for producing the carrier for developing electrostatic images according to claim 12. <6> The superficial velocity V of the fluidizing gas in the fluidized bed apparatus H However, the minimum fluidization velocity Umf must be between two and three times as large as the minimum fluidization velocity Umf. <5> 2. A method for producing the carrier for developing electrostatic images according to claim 1 . <7> <1> ~ <6> 13. A method for producing an electrostatic image developer, comprising the method for producing the carrier for developing an electrostatic image according to claim 12. Effect of the Invention
[0009] <1> According to the invention, a mixture containing a resin having a glass transition temperature Tg and a solvent is mixed with magnetic particles in a mixer, the mixture is heated to evaporate the solvent, a resin coating layer is formed on the surface of the magnetic particles, and resin-coated magnetic particles are obtained. Then, the resin-coated magnetic particles are heated to a temperature T A and a fluidized bed device for heating the resin-coated magnetic particles after step A to a temperature T B and a step C of cooling the resin-coated magnetic particles after the step B. A is lower than the glass transition temperature Tg-20°C and step B is not performed, or B is less than the glass transition temperature Tg-20°C or more than the glass transition temperature Tg+50°C, the resulting image is better inhibited from becoming dull. <2> According to the invention, in step A, the resin-coated magnetic particles are heated to a temperature T A The present invention provides a method for producing a carrier for developing electrostatic images, which is superior in suppressing color dullness in the obtained image compared to a case in which the stirring conditions in a mixer when disintegrating the toner particles while maintaining the above condition do not satisfy the condition of formula 2. <3> According to the invention, in step A, the resin-coated magnetic particles are heated to a temperature T A The present invention provides a method for producing a carrier for developing electrostatic images, which is superior in suppressing color dullness in the obtained image compared to a case in which the stirring conditions in a mixer when disintegrating the toner particles while maintaining the above formula 2 satisfy the condition of formula 2 but do not satisfy the condition of formula 2'.
[0010] <4> According to the present invention, the resin-coated magnetic particles after step A are heated to a temperature T B The resin-coated magnetic particles are then allowed to flow for less than 30 minutes while maintaining the temperature at T C to a glass transition temperature Tg-40° C. or lower, or the resin-coated magnetic particles after step A are cooled to a temperature T B After the resin-coated magnetic particles are allowed to flow for 30 minutes or more while maintaining the temperature T C The present invention provides a method for producing a carrier for developing electrostatic images, which is superior in suppressing color dullness in the resulting image, as compared with a method for cooling the carrier to a temperature lower than the glass transition temperature (Tg-40°C). <5> According to the invention, in step B, the resin-coated magnetic particles after step A are heated to a temperature T B The superficial velocity V of the fluidizing gas in the fluidized bed equipment when fluidizing the gas while maintaining the fluidization H The present invention provides a method for producing a carrier for developing electrostatic images, which is more excellent in suppressing color dullness in the resulting image than when the minimum fluidization velocity Umf (m / s) is more than 5 times the minimum fluidization velocity Umf. <6> According to the invention, in step B, the resin-coated magnetic particles after step A are heated to a temperature T B The superficial velocity V of the fluidizing gas in the fluidized bed equipment when fluidizing the gas while maintaining the fluidization H The present invention provides a method for producing a carrier for developing electrostatic images, which is superior in suppressing color dullness in the obtained image, as compared with a case in which the minimum fluidization velocity Umf (m / s) is more than 3 times and not more than 5 times the minimum fluidization velocity Umf. <7> According to the invention, a mixture containing a resin having a glass transition temperature Tg and a solvent is mixed with magnetic particles in a mixer, the mixture is heated to evaporate the solvent, a resin coating layer is formed on the surface of the magnetic particles, and resin-coated magnetic particles are obtained. Then, the resin-coated magnetic particles are heated to a temperature T Aand a fluidized bed device for heating the resin-coated magnetic particles after step A to a temperature T B and a step C of cooling the resin-coated magnetic particles after the step B. A is lower than the glass transition temperature Tg-20°C and step B is not performed, or B The present invention provides a method for producing an electrostatic image developer, which is superior in suppressing color dullness in the obtained image, as compared with a method for producing an electrostatic image developing carrier having a glass transition temperature (Tg) of less than Tg-20°C or more than Tg+50°C. [Brief description of the drawings]
[0011] [Figure 1] 1 is a schematic configuration diagram illustrating an example of an image forming apparatus according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram illustrating an example of a process cartridge that is detachably mounted to the image forming apparatus according to the present embodiment. [Diagram 3] 4 is a schematic graph showing the change in the load power value of the stirring blade and the change in the temperature inside the mixer over time in an example of a method for producing an electrostatic image developing carrier according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, embodiments of the present disclosure will be described. These descriptions and examples are merely illustrative of the embodiments, and are not intended to limit the scope of the embodiments.
[0013] In the present disclosure, a numerical range indicated using "~" indicates a range that includes the numerical values before and after "~" as the minimum and maximum values, respectively.
[0014] In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples.
[0015] In the present disclosure, the term "step" includes not only an independent step, but also a step that cannot be clearly distinguished from other steps, as long as the intended purpose of the step is achieved.
[0016] When embodiments of the present disclosure are described with reference to the drawings, the configuration of the embodiment is not limited to the configuration shown in the drawings. Furthermore, the sizes of the members in each drawing are conceptual, and the relative relationships between the sizes of the members are not limited to these.
[0017] In the present disclosure, each component may contain multiple types of corresponding substances. When referring to the amount of each component in a composition in the present disclosure, if multiple substances corresponding to each component are present in the composition, the total amount of the multiple substances present in the composition is meant unless otherwise specified.
[0018] In the present disclosure, the particles corresponding to each component may include multiple types. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component means the value for a mixture of the multiple types of particles present in the composition, unless otherwise specified.
[0019] In the present disclosure, "(meth)acrylic" means at least one of acrylic and methacrylic, and "(meth)acrylate" means at least one of acrylate and methacrylate.
[0020] In this disclosure, carbon black is not considered to be included in inorganic particles.
[0021] In this disclosure, "toner for developing electrostatic images" is also referred to as "toner", "carrier for developing electrostatic images" is also referred to as "carrier", and "electrostatic image developer" is also referred to as "developer".
[0022] <<Method for producing carrier for developing electrostatic image>> The method for producing the carrier for developing electrostatic images according to the present embodiment includes mixing a mixture containing a resin having a glass transition temperature Tg and a solvent with magnetic particles in a mixer, heating the mixture to evaporate the solvent and form a resin coating layer on the surfaces of the magnetic particles to obtain resin-coated magnetic particles, and then heating the resin-coated magnetic particles to a temperature T A and a fluidized bed device for heating the resin-coated magnetic particles after step A to a temperature T B and a step C of cooling the resin-coated magnetic particles after the step B. A and the temperature T B and each of the above-mentioned glass transition temperature Tg is equal to or higher than Tg-20°C and equal to or higher than Tg+50°C.
[0023] In the manufacture of carriers using the dip coating method, a mixed solution containing a resin having a glass transition temperature Tg and a solvent is mixed with magnetic particles in a mixer, the solvent is heated to evaporate the resin coating layer on the surface of the magnetic particles to obtain resin-coated magnetic particles, and then the resin-coated magnetic particles are crushed. When obtaining the resin-coated magnetic particles, the solvent is evaporated by heating, so that the temperature of the resin-coated magnetic particles is close to the glass transition temperature Tg of the resin. Therefore, when the obtained resin-coated magnetic particles are crushed while being cooled, the shear force applied to the resin-coated magnetic particles tends to cause peeling of the resin coating layer that is not completely fixed to the magnetic particles. Coating residue components such as resin pieces from the peeled resin coating layer are developed together with the toner, and color dullness due to the coating residue components may occur, especially in yellow toners and clear toners. Due to the increasing demand for quality, a further reduction in the coating residue components is desired to suppress the occurrence of color dullness in the obtained images.
[0024] In the method for producing a carrier for developing an electrostatic image according to the present embodiment, when crushing the resin-coated magnetic particles having a resin coating layer formed on the surface of the magnetic particles, the resin-coated magnetic particles are heated to a temperature T A When the crushed resin-coated magnetic particles are fluidized, the resin-coated magnetic particles are heated to a temperature T B Then, the resin-coated magnetic particles are cooled to a temperature T A and temperature T B are each independently set to Tg-20°C or more and Tg+50°C or less, based on the glass transition temperature Tg of the resin contained in the resin coating layer (or the resin contained in the mixed liquid). By crushing the resin-coated magnetic particles while maintaining such a temperature range (not cooling), fluidizing the crushed resin-coated magnetic particles, and then cooling the resin-coated magnetic particles, the resin-coated magnetic particles are cooled after the fixation of the resin coating layer to the magnetic particles is promoted, and it is presumed that peeling of the resin coating layer is reduced. As a result, in the manufacturing method of the electrostatic charge image developing carrier according to this embodiment, color dullness caused by the coating residue component is suppressed in the obtained image.
[0025] Hereinafter, each step in the method for producing the electrostatic image developing carrier according to this embodiment will be described in detail.
[0026] <Process A> The method for producing the carrier for developing electrostatic images according to the present embodiment involves mixing magnetic particles with a mixed liquid containing a resin having a glass transition temperature Tg and a solvent in a mixer, heating the mixture to evaporate the solvent and form a resin coating layer on the surfaces of the magnetic particles to obtain resin-coated magnetic particles, and then heating the resin-coated magnetic particles to a temperature T A The method further comprises a step A of disintegrating the mixture while maintaining the temperature. Here, the temperature T A satisfies the glass transition temperature Tg-20°C or more and the glass transition temperature Tg+50°C or less. Hereinafter, when the term "glass transition temperature Tg" is mentioned, it refers to the glass transition temperature Tg of the resin contained in the mixed liquid (the resin contained in the resin coating layer). In addition, a "mixture containing a resin having a glass transition temperature Tg and a solvent" is also simply called a "mixture."
[0027] That is, in step A, when crushing the resin-coated magnetic particles formed by forming a resin coating layer on the surface of the magnetic particles, the temperature of the resin-coated magnetic particles is set to a temperature Tg in the range of Tg-20°C to Tg+50°C based on the glass transition temperature Tg of the resin contained in the mixed liquid (the resin contained in the resin coating layer). A This should be done while maintaining the same level. For example, if the glass transition temperature Tg of a resin is 110°C, then the temperature T A The temperature may be 90°C or higher and 160°C or lower. In this embodiment, when the mixed liquid contains two or more types of resins (when the resin coating layer contains two or more types of resins), the glass transition temperature Tg of the resin is the Tg of the resin having the lower glass transition temperature among the two or more types of resins. The resin-coated magnetic particles are heated to a temperature T A To maintain the temperature T A The temperature of the mixer body can be adjusted so that
[0028] temperature T A is measured as follows: That is, temperature T A The temperature is measured by placing a thermometer at a position inside the mixer that can come into contact with the resin-coated magnetic particles, or by placing a thermometer at a position that does not come into contact with the resin-coated magnetic particles and measuring the atmospheric temperature inside the mixer.
[0029] From the viewpoint of further suppressing color dullness in the resulting image, the temperature T A is preferably not lower than glass transition temperature Tg-20° C. and not higher than glass transition temperature Tg+20° C., and more preferably not lower than glass transition temperature Tg-15° C. and not higher than glass transition temperature Tg. This is because in step A, if too much stirring work is applied at a temperature 50° C. above the glass transition temperature Tg, peeling of the resin coating layer formed on the surface of the magnetic particles will be caused, so a temperature near Tg is preferable.
[0030] From the viewpoint of further suppressing color dullness of the resulting image, it is preferable to crush the resin-coated magnetic particles with a weak shear force. Specifically, in step A, the resin-coated magnetic particles are crushed using a mixer having an agitating blade at a temperature T A It is preferable that the stirring conditions in the mixer during disintegration while maintaining the above condition satisfy the conditions of the following formula 1 and the following formula 2. 0.2≦Peripheral speed of impeller πDN(m / s)≦2.0 Formula 1 5×10 2 ≦Mixing work load (circumferential speed πDN × mixing time T) ≦ 1.5 × 10 3 formula 2 In Equation 1 and Equation 2, D represents the diameter (m) of the impeller, N represents the rotation speed (rps) of the impeller, and T represents the time (s) from the point at which the load power value of the impeller before drying of the solvent increases as the drying progresses and falls to 1.3 times or less the value before drying when drying is completed, to the point at which mixing in the mixer is terminated. Note that π represents the ratio of the circumference of a circle to its circumference.
[0031] In the step A, for example, fluctuations in the load power value of the stirring blades are likely to occur as shown in FIG. FIG. 3 is a schematic graph showing the fluctuation in the load power value of the stirring blade and the fluctuation in the temperature inside the mixer over time in an example of the method for producing an electrostatic image developing carrier according to the present embodiment. The vertical axis on the left side of FIG. 3 represents the load power value (kW) of the mixing blade, the vertical axis on the right side represents the temperature inside the mixer (° C.), and the horizontal axis represents the elapsed time (min).
[0032] At T0 in Fig. 3, a mixed liquid containing a resin having a glass transition temperature Tg and a solvent and magnetic particles are put into a mixer, and from T0 to T1, the mixed liquid and magnetic particles are mixed. Then, in Fig. 3, from T1 to T2, the mixed liquid is heated and, if necessary, reduced pressure is applied to evaporate the solvent contained in the mixed liquid, forming a resin coating layer on the surface of the magnetic particles to obtain resin-coated magnetic particles, and the resin-coated magnetic particles are dried until completion, and from T2 to T3, the dried resin-coated magnetic particles are crushed. Furthermore, at T3, the mixing in the mixer is completed, and the carrier is taken out of the mixer.
[0033] The fluctuation of the load power value of the stirring impeller shown in FIG. 3 is as follows. From T0 to T1, the load power value of the stirring impeller is almost constant. From T1 to T2, as the solvent evaporates, the viscosity of the mixture of the mixed liquid and the magnetic particles in the mixer increases, and the load power value of the impeller continues to rise until the drying of the resin-coated magnetic particles is complete. When the drying of the resin-coated magnetic particles is complete, the load power value of the impeller suddenly decreases to a value less than 1.3 times the load power value of the impeller from T0 to T1. From T2 to T3, the load power value of the stirring impeller again becomes almost constant. The above T is the time from T2 to T3.
[0034] The temperature fluctuations in the mixer shown in FIG. 3 are as follows. From T0 to T1, the temperature is gradually increased to a set temperature (for example, the jacket temperature). From T1 to T2, the temperature does not rise steadily due to the heat of vaporization of the solvent, but overall the temperature rises gradually as the drying of the resin-coated magnetic particles progresses. From T2 to T3, the temperature of the resin-coated magnetic particles is T A The set temperature (for example, the jacket temperature) is controlled so that it is within the range.
[0035] The mixer used in step A may be any mixer having an agitating blade, and any known mixer may be used. From the viewpoint of drying properties, however, a vacuum mixer is preferable. Moreover, the mixer used in step A is preferably a batch mixer, more preferably a batch vacuum mixer, from the viewpoints of mixing properties and suppression of color dullness in the resulting image. Furthermore, as the batch mixer, a blade type kneader is preferred, and the direction of the rotation axis of the blade may be vertical or horizontal. Vertical types include a spiral mixer (manufactured by Aikosha Seisakusho Co., Ltd.) and a planetary mixer (manufactured by Inoue Seisakusho Co., Ltd.), and horizontal types include a kneader (manufactured by Inoue Seisakusho Co., Ltd.). Among them, a two-shaft horizontal kneader is particularly preferred from the viewpoints of mixing ability and suppression of color dullness of the obtained image. The mixer preferably has a temperature control structure capable of heating and cooling the inside of the mixing vessel under reduced pressure, and a mechanism capable of detecting the stirring power value of the stirring blades. The temperature control structure is not particularly limited, but a jacket structure is preferred.
[0036] The shape of the stirring blade in the mixer is not particularly limited, but examples thereof include Banbury type, Sigma type, Z type, spiral type, and fishtail type. The diameter D of the impeller is not particularly limited and may be any size suitable for the mixer to be used. In addition, the diameter D of the impeller in this embodiment is the maximum outer diameter of the part that the impeller passes through as it rotates on a plane perpendicular to the rotation axis. From the viewpoint of the production speed of the resin-coated magnetic particles and the suppression of discoloration of the resulting images, the rotation speed N of the stirring blade, for example, in the mixer in the examples, is preferably 10 rpm or more and 200 rpm or less, more preferably 15 rpm or more and 150 rpm or less, even more preferably 20 rpm or more and 100 rpm or less, and particularly preferably 40 rpm or more and 60 rpm or less. The clearance (gap) between the stirring tank and the stirring blade in the mixer is not particularly limited and is determined according to the size of the mixer used, but if the clearance is large, not only will the resin-coated magnetic particles accumulated at the bottom not be completely crushed, but the shear force of the crushing is determined not only by the peripheral speed of the stirring blade and the stirring work load, but also by the clearance. Therefore, the narrower the clearance, the better, but because there is a limit to the clearance due to the constraints of the production of the device, the clearance between the outer periphery of the stirring blade and the stirring tank is preferably 5% or less, more preferably 3.5% or less, in terms of the value of clearance / diameter of the stirring blade.
[0037] The load power value of the mixing blade before the drying of the solvent increases as the drying progresses, and the time T from the point at which the load power value falls to 1.3 times or less the value before drying when the drying is completed to the point at which mixing in the mixer is completed is set to 5×10 2 ≦Mixing work load (circumferential speed πDN × mixing time T) ≦ 1.5 × 10 3 The mixing time T must be determined according to the peripheral speed so as to satisfy formula 2. For example, in the mixer in the examples, the mixing time is preferably from 5 to 100 minutes, more preferably from 8 to 80 minutes, even more preferably from 15 to 60 minutes, and particularly preferably from 15 to 45 minutes. During step A, it is preferable to continue stirring with a stirring blade.
[0038] In step A, the resin-coated magnetic particles are mixed in a mixer having an agitating blade at a temperature T A The stirring conditions in the mixer when disintegrating the mixture while maintaining the above condition preferably satisfy the condition of the following formula 1', and more preferably satisfy the condition of the following formula 1". 0.3≦the peripheral speed of the stirring blade πDN (m / s)≦1.0 Formula 1' 0.5≦the peripheral speed of the impeller πDN(m / s)≦0.8 Formula 1"
[0039] In step A, the resin-coated magnetic particles are mixed in a mixer having an agitating blade at a temperature T AThe stirring conditions in the mixer during disintegration while maintaining the above condition preferably satisfy the condition of the following formula 2'. In other words, the condition of formula (2) is preferably the condition of the following formula 2'. 7×10 2 ≦Mixing work load (circumferential speed πDN × mixing time T) ≦ 1 × 10 3 formula 2'
[0040] In step A, the solvent may be evaporated by heating under normal pressure, under reduced pressure, or by heating under reduced pressure. Heating under reduced pressure is preferred because it allows drying to be performed without causing the temperature to rise above the boiling point of the solvent and the glass transition temperature (Tg) of the resin. The air pressure inside the mixer in step A is not particularly limited and may be appropriately selected depending on the glass transition temperature Tg of the resin and the solvent used. From the viewpoints of the evaporation rate of the solvent and suppression of color dullness in the obtained image, the air pressure is preferably from 0.1 kPa-a to 80 kPa-a, and more preferably from 5 kPa-a to 60 kPa-a. Note that kPa-a represents the atmospheric pressure (kPa) based on absolute pressure. The pressure reducing means in the mixer is not particularly limited, and known pressure reducing means such as a pressure reducing pump can be used. The evaporated solvent may be recovered by a solvent recovery means such as a cold trap.
[0041] When the disintegration of the resin-coated magnetic particles in step A is completed, the resin-coated magnetic particles are removed from the mixer. The temperature of the resin-coated magnetic particles when removed from the mixer is T A maintains its position.
[0042] The amount of the mixed liquid and the amount of the magnetic particles used in step A are not particularly limited, and may be appropriately selected depending on the dispersing machine used, etc. The amount ratio of the mixed liquid and the magnetic particles may be appropriately selected depending on the concentration of the mixed liquid, the thickness of the resin coating layer to be formed, and the like. Furthermore, in step A, other components to be contained in the resin coating layer, such as particles, in addition to the mixed liquid and the magnetic particles, may be added to the mixer. The mixed liquid containing the resin and the solvent, the magnetic particles, and other components used in step A will be described in detail below.
[0043] <Process B> In the method for producing a carrier for developing an electrostatic image according to the present embodiment, the resin-coated magnetic particles after step A are heated to a temperature T B The method further comprises a step B of flowing the mixture while maintaining the temperature. Here, the temperature T B satisfies the glass transition temperature Tg-20°C or more and the glass transition temperature Tg+50°C or less.
[0044] That is, in step B, when the resin-coated magnetic particles crushed in step A are fluidized, the temperature of the resin-coated magnetic particles is set to a temperature Tg in the range of Tg-20°C to Tg+50°C based on the glass transition temperature Tg of the resin contained in the mixed liquid (the resin contained in the resin coating layer). B This should be done while maintaining the same level. For example, if the glass transition temperature Tg of a resin is 110°C, then the temperature T B The temperature may be 90°C or higher and 160°C or lower. The resin-coated magnetic particles are heated to a temperature T B To maintain this temperature, the temperature of the fluidizing gas in the fluidized bed apparatus, the jacket temperature of the fluidized bed apparatus, or both may be adjusted.
[0045] temperature T B is measured as follows: That is, temperature T B A thermometer is placed in the upper part of the fluidizing device or in the exhaust piping of the fluidizing gas, and the gas temperature is measured immediately after the resin-coated magnetic particles are fluidized.
[0046] In addition, the temperature T A and temperature T in process B Bmay be the same or different temperatures as long as they are in the range of glass transition temperature Tg-20°C or more and glass transition temperature Tg+50°C or less. From the viewpoint of further suppressing the color dullness of the resulting image, for example, the temperature T A and temperature T in process B B The difference between the temperatures is preferably 15° C. or less, and more preferably 10° C. or less. This is because the smaller the temperature difference, the shorter the time required to obtain the effect of suppressing color dullness of the image.
[0047] From the viewpoint of further suppressing color dullness in the resulting image, the temperature T B It is preferable that the range is from glass transition temperature Tg-20°C to glass transition temperature Tg+20°C, and more preferably from glass transition temperature Tg-15°C to glass transition temperature Tg°C. Like in step A, if too much stirring work is applied at a temperature 50° C. above the glass transition temperature Tg, the resin coating layer formed on the surface of the magnetic particles will peel off, so a temperature near Tg is preferable.
[0048] From the viewpoint of further suppressing color dullness in the resulting image, the temperature T B The flow time of the resin-coated magnetic particles when kept at this temperature is correlated with the temperature from the viewpoint of fixing the resin coating layer. The higher the temperature, the shorter the flow time can be, but 20 minutes or more is preferable, 30 minutes or more is more preferable, and 45 minutes or more is even more preferable. Also, the temperature T B The upper limit of the flow time of the resin-coated magnetic particles while maintained at this temperature is, for example, 360 minutes, since there is a concern that the amount of free resin in the resin coating layer will increase due to contact between the resin-coated magnetic particles caused by the flow, and a time of 120 minutes or less is preferable. temperature T B The flow time of the resin-coated magnetic particles while maintained at this temperature is preferably from 20 to 120 minutes, more preferably from 30 to 90 minutes, and even more preferably from 45 to 60 minutes.
[0049] <Process C> The method for producing a carrier for developing an electrostatic image according to this embodiment includes a step C of cooling the resin-coated magnetic particles after the step B. The step C is preferably carried out in a fluidized bed apparatus subsequent to the step B. Here, the cooling temperature of the resin-coated magnetic particles is, for example, preferably the glass transition temperature Tg-30° C. or lower, and more preferably the glass transition temperature Tg-40° C. or lower. The lower limit of the cooling temperature of the resin-coated magnetic particles is room temperature, for example, 20° C. Here, the cooling temperature refers to the temperature that the resin-coated magnetic particles reach by cooling in the fluidized bed apparatus. In this embodiment, from the viewpoint of further suppressing color dullness of the obtained image, in step B, the resin-coated magnetic particles after step A are heated to a temperature T B The resin-coated magnetic particles are then allowed to flow for 30 minutes or more while maintaining the temperature T C It is preferable to cool the mixture to a glass transition temperature (Tg-40°C) or lower.
[0050] In addition, the cooling time for the resin-coated magnetic particles is not particularly limited, but from the viewpoint of the carrier production speed and the suppression of color dullness in the obtained image, it is preferably from 10 minutes to 360 minutes, more preferably from 30 minutes to 240 minutes, and particularly preferably from 60 minutes to 150 minutes.
[0051] A fluidized bed apparatus is used in steps B and C. The resin-coated magnetic particles are fluidized using a fluidized bed apparatus capable of mixing without stirring, and then cooled, which can promote the fixation of the resin coating layer to the magnetic particles. The fluidized bed apparatus is not particularly limited, and may be a fluidized bed apparatus using only fluidizing air or a vibration fluidized bed apparatus in which fluidization is assisted by vibration.
[0052] The fluidized bed apparatus is operated at the bottom of the apparatus at the temperature T B Or T C Any device can be used as long as it can discharge a temperature-controlled and dehumidified gas (also called a fluidizing gas) into which the resin-coated magnetic particles are subjected. In other words, the fluidized bed device has a mechanism for heating or cooling the gas. The mechanism for heating the gas includes an air heater. For example, an air heater installed outside the body of the fluidized bed device can heat the gas to a temperature T B By supplying a gas heated to a temperature of T B The liquid may be allowed to flow while maintaining the liquid level. The mechanism for cooling the gas is not particularly limited. The resin-coated magnetic particles may be cooled (for example, to a glass transition temperature (Tg) - 40°C or less) by supplying room temperature gas to the bottom of the device. Furthermore, the body of the fluidized bed apparatus may have a jacket structure, and hot water or cold water may be circulated through the jacket to heat or cool the gas.
[0053] It is preferable that step B is carried out consecutively after step A. Specifically, it is preferable to feed the resin-coated magnetic particles which have been disintegrated in step A directly from the mixer into the fluidized bed apparatus.
[0054] The temperature of the resin-coated magnetic particles in the fluidized bed device can be adjusted by the heat transfer efficiency, which is determined by the stirring state in the tank, based on the temperature of the resin-coated magnetic particles fed into the device, the temperature of the fluidizing gas, and the superficial velocity of the fluidizing gas based on the minimum fluidizing velocity Umf described below. For example, the higher the temperature of the fluidizing gas and the faster the superficial velocity, the faster the temperature of the resin-coated magnetic particles can be raised in a short time.
[0055] Temperature T by fluidized bed equipment B When the resin-coated magnetic particles are flowing while being maintained at temperature T B If the temperature exceeds the glass transition temperature Tg, the resin-coated magnetic particles become susceptible to the above-mentioned stresses such as friction and shear force, and the resin coating layer becomes susceptible to peeling. In order to reduce the friction between the resin-coated magnetic particles and the shear force that the resin-coated magnetic particles receive from the gas, the resin-coated magnetic particles after crushing are heated to a temperature T BThe superficial velocity V of the fluidizing gas in the fluidized bed device when fluidizing while maintaining H Just reduce (m / s). Specifically, in step B, the resin-coated magnetic particles after step A are heated to a temperature T B The superficial velocity V of the fluidizing gas in the fluidized bed equipment when fluidizing the gas while maintaining the fluidization H (m / s) is preferably 1 to 5 times the minimum fluidization velocity Umf, and more preferably 2 to 3 times the minimum fluidization velocity Umf.
[0056] The minimum fluidization velocity Umf can be experimentally determined from the flow rate at the point where the pressure of the fluidizing gas increases and then stabilizes, using the following formula: Minimum fluidization velocity Umf (m / s) = flow rate at the change point (m 3 / s) ÷ cross-sectional area of fluidizer (m 2 )
[0057] The resin-coated magnetic particles are heated to a temperature T B The superficial velocity V of the fluidizing gas when the gas is flowed while being maintained at H There is no particular limitation on the speed, but it is preferably 10 mm / s or more and 50 mm / s or less, and more preferably 20 mm / s or more and 30 mm / s or less.
[0058] In addition, the superficial velocity V of the fluidizing gas in the fluidized bed device when cooling the resin-coated magnetic particles C From the viewpoint of improving cooling efficiency, (m / s) is preferably 2 to 10 times the minimum fluidization velocity Umf, and more preferably 5 to 10 times the minimum fluidization velocity Umf. In addition, from the viewpoint of improving the cooling efficiency, the superficial velocity V of the fluidizing gas in the fluidized bed device when cooling the resin-coated magnetic particles is C (m / s) is the temperature T B The superficial velocity V of the fluidizing gas in the fluidized bed equipment when fluidizing the gas while maintaining the fluidization H It is preferable that the axial length is greater than (m / s).
[0059] The fluidizing gas in the fluidizer is not particularly limited, and air, nitrogen, argon, etc. can be used. Among them, air is preferable. Furthermore, the fluidizing gas is preferably a dehumidified gas, preferably a gas with a relative humidity of 30% or less, more preferably a gas with a relative humidity of 20% or less, and particularly preferably a gas with a relative humidity of 10% or less.
[0060] By going through the above steps A, B, and C, an electrostatic image developing carrier having a resin coating layer on the surface of magnetic particles is obtained.
[0061] <Other processes> The method for producing the electrostatic image developing carrier according to this embodiment may include steps other than step A, step B, and step C. The other steps are not particularly limited, and may include known steps in the production method of a carrier for developing electrostatic images. The method for producing the electrostatic image developing carrier according to the present embodiment preferably further includes, for example, a step of preparing magnetic particles, and a step of preparing a mixed liquid containing a resin and a solvent.
[0062] <Carrier properties> The volume average particle size of the electrostatic image developing carrier obtained by the method for producing an electrostatic image developing carrier according to this embodiment is preferably 10 μm or more and 500 μm or less, more preferably 15 μm or more and 100 μm or less, and particularly preferably 20 μm or more and 60 μm or less. The volume average particle diameter of the magnetic particles and carrier in this embodiment is a value measured by a laser diffraction particle size distribution measuring device LA-700 (manufactured by Horiba, Ltd.) Specifically, for a particle size range (channel) into which the particle size distribution obtained by the measuring device is divided, the particle diameter at which the cumulative volume distribution is subtracted from the small particle size side and the cumulative 50% is defined as the volume average particle diameter.
[0063] The amount of the resin coating layer in the electrostatic image developing carrier obtained by the method for producing an electrostatic image developing carrier according to this embodiment is, from the viewpoints of thickness stability of the resin coating layer and chargeability, preferably from 0.5 mass % to 10 mass %, and more preferably from 1 mass % to 5 mass %, relative to the total mass of the carrier.
[0064] The amount of free resin in the electrostatic image developing carrier obtained by the method for producing an electrostatic image developing carrier according to this embodiment is, from the viewpoint of suppressing color dullness in the obtained image, preferably 300 ppm or less, more preferably 100 ppm or less, even more preferably 50 ppm or less, and particularly preferably 30 ppm or less.
[0065] In this embodiment, the method for measuring the amount of free resin in the carrier for developing an electrostatic image is as follows. A certain amount of carrier was weighed out, dispersed in water, and the dispersion was filtered while the carrier was fixed with a magnet. The filter paper was dried, and the amount of free resin was calculated from the difference in mass before and after the filter paper and the weighed amount of carrier using the following formula. Free resin amount (ppm) = Increase in filter paper amount (g) ÷ Carrier amount (g)
[0066] The proportion of aggregates after 75 μm sieving in the electrostatic image developing carrier obtained by the manufacturing method for the electrostatic image developing carrier according to this embodiment is preferably as small as possible, and from the viewpoint of suppressing color dullness in the obtained image, is preferably 5% by number or less, more preferably 1% by number or less, even more preferably 0.1% by number or less, and particularly preferably 0.01% by number or less.
[0067] In this embodiment, the method for measuring the proportion of aggregates in the electrostatic image developing carrier after sieving through a 75 μm sieve is as follows. The carrier is sieved using a sieve with 75 μm openings, and the sieved carrier is spread out so as not to overlap as much as possible. A scanning electron microscope (SEM) photograph is taken at 350x magnification, and the ratio of the number of carrier particles that have not been broken down into primary particles to the number of carrier particles in one field of view is measured.
[0068] In this embodiment, the exposed area ratio of the magnetic particles in the carrier for developing electrostatic images is preferably 3% to 30%, more preferably 4% to 25%, and even more preferably 5% to 20%. The exposed area ratio of the magnetic particles in the carrier can be controlled by the amount of resin used to form the resin coating layer, and the greater the amount of resin relative to the amount of magnetic particles, the smaller the exposed area ratio. That is, in this embodiment, the coverage rate of the resin coating layer on the surface of the carrier for developing electrostatic images is preferably 70% or more and 97% or less, more preferably 75% or more and 96% or less, and even more preferably 80% or more and 95% or less.
[0069] The exposed area ratio of the magnetic particles and the coverage of the resin coating layer on the carrier surface are values determined by the following method. A target carrier and magnetic particles from which the resin coating layer has been removed from the target carrier are prepared. Methods for removing the resin coating layer from the carrier include, for example, a method for removing the resin coating layer by dissolving the resin component with an organic solvent, and a method for removing the resin coating layer by eliminating the resin component by heating at about 800°C. The carrier and magnetic particles are each used as measurement samples, and the ratios (atomic %) of Fe, C, and O on the sample surface are quantified by XPS, and the exposed area ratio (%) of the magnetic particles is calculated by (Fe ratio of the carrier) ÷ (Fe ratio of the magnetic particles) × 100. The coverage (%) of the resin coating layer is calculated by (100-exposed area rate of the magnetic particles).
[0070] In this embodiment, the fluidity of the carrier for developing electrostatic images is preferably from 20 sec / 50 g to 50 sec / 50 g, more preferably from 22 sec / 50 g to 35 sec / 50 g, and particularly preferably from 25 sec / 50 g to 30 sec / 50 g, from the viewpoint of suppressing density change in the resulting image. The fluidity of the electrostatic image developing carrier in this embodiment is a value measured at 25° C. and 50% RH in accordance with JIS Z2502 (2020).
[0071] <Career Structure> The electrostatic image developing carrier obtained by the method for producing an electrostatic image developing carrier according to this embodiment has a resin coating layer on the surface of the magnetic particles. The configuration of the electrostatic image developing carrier in this embodiment will be described below.
[0072] [Magnetic particles] The magnetic particles used in this embodiment are known magnetic particles. Known materials are used as the magnetic particles, and examples of such materials include magnetic metals such as iron, nickel, and cobalt, alloys of these magnetic metals with manganese, chromium, and rare earth elements, magnetic oxides such as iron oxide, ferrite, and magnetite, and resin-dispersed magnetic particles in which a conductive material is dispersed in a matrix resin. Examples of resins used in the resin-dispersed magnetic particles include, but are not limited to, polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymer, styrene-acrylic acid copolymer, straight silicone resin containing organosiloxane bonds or modified products thereof, fluororesin, polyester, polycarbonate, phenolic resin, epoxy resin, and the like. Among these, the magnetic particles are preferably magnetic oxide particles, and more preferably ferrite particles.
[0073] -Ferrite particles- Ferrite is generally classified as (MO) X (Fe2O3) Y In the formula, M is mainly MN, but it is also possible to combine at least one or several selected from the group consisting of Li, Ca, Sr, SN, Cu, ZN, Ba, Fe, Ti, Ni, Al, Co, and Mo. In addition, X and Y indicate a molar ratio and satisfy the condition X+Y=100. In general, the properties of ferrite particles change depending on their composition and structure.
[0074] The ferrite particles used in this embodiment are not particularly limited, but can be prepared, for example, as follows. The powder of the metal oxide or metal salt as the raw material is mixed and calcined using a rotary kiln or the like to obtain a calcined product. Here, examples of the metal oxide or metal salt as the raw material include Fe2O3, MNO2, SrCO3, Mg(OH)2, etc., and for example, the amount of SrCO3 is adjusted to make the strontium content in the ferrite particles 0.1 mass% or more and 1.0 mass% or less. The calcination temperature can be 800°C or more and 1,000°C or less, and the calcination time can be 6 hours or more and 10 hours or less. The calcination temperature can be 800°C or more and 1,000°C or less, and the calcination time can be 6 hours or more and 10 hours or less. The obtained calcined product is ground by a known grinding method, specifically, by adding polyvinyl alcohol, water, a surfactant, and an antifoaming agent, and grinding it with a mortar, a ball mill, a jet mill, or the like. The calcined product is ground until the average particle size is, for example, 4 μm or more and 10 μm or less. Next, the pulverized pre-calcined product is granulated and dried using a spray dryer. This dried pre-calcined product is calcined again (re-calcined) to remove the contained organic matter, thereby obtaining a re-calcined product. The temperature of the re-calcination can be 800°C or higher and 1,000°C or lower, and the time of the re-calcination can be 5 hours or higher and 10 hours or lower. The obtained re-calcined product is added with polyvinyl alcohol, water, a surfactant, and an antifoaming agent, and pulverized using a mortar, ball mill, jet mill, or the like. The pulverized pre-calcined product is pulverized, for example, until the average particle size is 4 μm or higher and 8 μm or lower. Next, the pulverized re-calcined product is granulated and dried using a spray dryer. The dried granulated product is calcined (main calcination) using a rotary kiln or the like to obtain a main calcined product. Here, the temperature of the main calcination can be 1,000°C or higher and 1,400°C or lower, and the time of the main calcination can be 3 hours or higher and 6 hours or lower. The fired product is then subjected to a crushing step and a classification step to obtain ferrite particles.
[0075] The volume average particle size of the magnetic particles used in this embodiment is preferably 10 μm or more and 500 μm or less, more preferably 15 μm or more and 100 μm or less, and particularly preferably 20 μm or more and 60 μm or less. The average particle size of the fired product or ferrite particles refers to a value measured using a laser diffraction / scattering particle size distribution analyzer (LS Particle Size Analyzer: LS13 320, manufactured by BECKMAN COULTER Co., Ltd.). The particle size distribution obtained is divided into particle size ranges (channels), and the cumulative distribution is subtracted from the small particle size side, and the particle size at which the cumulative 50% is determined as the volume average 50% particle size.
[0076] The BET specific surface area of the magnetic particles is set to 0.10 m from the viewpoints of long-term image quality stability and suppression of density change. 2 / g or more 0.35m 2 / g or less, and 0.11m 2 / g or more 0.28m 2 / g or less is more preferable, and 0.12m 2 / g or more 0.24m 2 In addition, when the coating resin is in the above range, an appropriate amount of the coating resin enters the gaps between the magnetic particles, and deterioration of the resin coating layer due to an anchoring effect can be suppressed, resulting in excellent long-term image quality stability and suppression of density change.
[0077] The BET specific surface area of the magnetic particles is measured using a SA3100 specific surface area measuring device (manufactured by Beckman Coulter) with nitrogen substitution and a three-point method. Specifically, 5 g of magnetic particles are placed in a cell, degassed at 60°C for 120 minutes, and then a mixed gas of nitrogen and helium (30:70) is used. More specifically, the method for separating the magnetic particles from the carrier is as follows: for example, 20 g of the resin-coated carrier is placed in 100 mL of toluene. Ultrasonic waves are applied at 40 kHz for 30 seconds. The magnetic particles and the resin solution are separated using any filter paper according to the particle size. 20 mL of toluene is poured over the magnetic particles remaining on the filter paper to wash them. Next, the magnetic particles remaining on the filter paper are collected. The collected magnetic particles are similarly placed in 100 mL of toluene and ultrasonic waves are applied at 40 kHz for 30 seconds. The magnetic particles are similarly filtered, washed with 20 mL of toluene, and then collected. This is repeated 10 times in total. Finally, the collected magnetic particles are dried, and the BET specific surface area is measured under the above conditions.
[0078] The arithmetic mean height Ra (JIS B0601:2001) of the roughness curve of the magnetic particles is preferably 0.1 μm or more and 1 μm or less, and more preferably 0.2 μm or more and 0.8 μm or less. The arithmetic mean height Ra of the roughness curve of a magnetic particle is determined by observing the magnetic particle at an appropriate magnification (for example, 1000x magnification) using a surface shape measuring device (for example, Keyence Corporation's "Ultra-Deep Color 3D Shape Measuring Microscope VK-9700"), obtaining a roughness curve at a cutoff value of 0.08 mm, and extracting a reference length of 10 μm from the roughness curve in the direction of the average line. The Ra of 100 magnetic particles is calculated as the arithmetic mean.
[0079] The magnetic force of the magnetic particles is preferably 50 emu / g or more, more preferably 60 emu / g or more, in terms of saturation magnetization in a magnetic field of 3,000 oersteds. The saturation magnetization is measured using a vibrating sample magnetic measuring device VSMP10-15 (manufactured by Toei Kogyo Co., Ltd.). The measurement sample is packed in a cell with an inner diameter of 7 mm and a height of 5 mm and set in the device. The measurement is performed by applying a magnetic field and sweeping up to a maximum of 3,000 oersteds. The applied magnetic field is then reduced, and a hysteresis curve is prepared on a recording paper. The saturation magnetization, residual magnetization, and retentivity are determined from the curve data.
[0080] The volume resistivity of magnetic particles is 1×10 5 Ω cm or more 1×10 9 Ω cm or less is preferable, and 1×10 7 Ω cm or more 1×109 Ω·cm or less is more preferable. The volume resistivity (Ω·cm) of magnetic particles is measured as follows: 2 The object to be measured is placed flat on the surface of the circular jig on which the electrode plate is arranged, with a thickness of 1 mm to 3 mm, to form a layer. 2 The layer is sandwiched between two electrode plates. In order to eliminate any gaps between the objects being measured, a 4 kg load is placed on the electrode plate placed on the layer, and then the thickness of the layer (cm) is measured. Both the top and bottom electrodes of the layer are connected to an electrometer and a high-voltage power supply generator. A high voltage is applied to both electrodes so that the electric field is 103.8 V / cm, and the current value (A) that flows at this time is read. The measurement environment is a temperature of 20°C and a relative humidity of 50%. The formula for calculating the volumetric electrical resistivity (Ω·cm) of the object being measured is as shown below. R=E×20 / (I-I0) / L In the above formula, R is the volume resistivity (Ω cm) of the object to be measured, E is the applied voltage (V), I is the current value (A), I0 is the current value (A) at an applied voltage of 0 V, and L is the layer thickness (cm). The coefficient 20 is the area of the electrode plate (cm 2 )
[0081] [Resin coating layer] The electrostatic image developing carrier in this embodiment has a resin coating layer that coats the magnetic particles.
[0082] Examples of resins that make up the resin coating layer include styrene-acrylic acid copolymers; polyolefin resins such as polyethylene and polypropylene; polyvinyl or polyvinylidene resins such as polystyrene, acrylic resin, polyacrylonitrile, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl carbazole, polyvinyl ether, and polyvinyl ketone; vinyl chloride-vinyl acetate copolymers; straight silicone resins or modified products thereof consisting of organosiloxane bonds; fluororesins such as polytetrafluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, and polychlorotrifluoroethylene; polyesters; polyurethanes; polycarbonates; amino resins such as urea-formaldehyde resins; and epoxy resins. In particular, from the viewpoints of electrostatic charge, control of external additive adhesion, and suppression of concentration change, it is preferable that the resin constituting the resin coating layer contains an acrylic resin, it is more preferable that the acrylic resin is contained in an amount of 50 mass% or more, based on the total mass of the resin in the resin coating layer, and it is particularly preferable that the acrylic resin is contained in an amount of 80 mass% or more, based on the total mass of the resin in the resin coating layer.
[0083] From the viewpoint of suppressing concentration change, the resin coating layer preferably contains an acrylic resin having an alicyclic structure. As a polymerization component of the acrylic resin having an alicyclic structure, a lower alkyl ester of (meth)acrylic acid (for example, an alkyl (meth)acrylate ester having 1 to 9 carbon atoms in the alkyl group) is preferable, and specific examples thereof include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. These monomers may be used alone or in combination of two or more. The acrylic resin having an alicyclic structure preferably contains cyclohexyl (meth)acrylate as a polymerization component. The content of the monomer unit derived from cyclohexyl (meth)acrylate contained in the acrylic resin having an alicyclic structure is preferably 75% by mass or more and 100% by mass or less, more preferably 85% by mass or more and 100% by mass or less, and even more preferably 95% by mass or more and 100% by mass or less, based on the total mass of the acrylic resin having an alicyclic structure.
[0084] The weight average molecular weight of the resin contained in the resin coating layer is preferably less than 300,000, more preferably less than 250,000, even more preferably from 5,000 to less than 250,000, and particularly preferably from 10,000 to 200,000. When in the above range, the smoothness of the resin coating surface of the carrier is increased, so that the amount of external additives attached to the carrier is reduced, and the concentration change suppression property is more excellent.
[0085] The resin coating layer may contain conductive particles for the purpose of controlling electrostatic charge and resistance. Examples of the conductive particles include carbon black and inorganic particles having electrical conductivity, which will be described later. Among these, carbon black is preferred. From the viewpoint of electrostatic chargeability, the content of the conductive particles contained in the resin coating layer is preferably 0.1 mass % or more and 30 mass % or less, more preferably 0.5 mass % or more and 20 mass % or less, and even more preferably 1 mass % or more and 10 mass % or less, relative to the total mass of the resin coating layer.
[0086] The resin coating layer may also contain inorganic particles. Examples of inorganic particles contained in the resin coating layer include metal oxide particles such as silica, titanium oxide, zinc oxide, and tin oxide; metal compound particles such as barium sulfate, aluminum borate, and potassium titanate; and metal particles such as gold, silver, and copper. Among these, silica particles are preferred from the viewpoint of suppressing concentration changes.
[0087] From the viewpoint of suppressing concentration change, the arithmetic mean particle size of the inorganic particles in the resin coating layer is preferably 5 Nm or more and 90 Nm or less, more preferably 5 Nm or more and 70 Nm or less, even more preferably 5 Nm or more and 50 Nm or less, and particularly preferably 8 Nm or more and 50 Nm or less.
[0088] In this embodiment, the average particle size of the inorganic particles contained in the resin coating layer is determined by the following method. The carrier is embedded in epoxy resin and cut with a microtome to prepare a carrier cross section. SEM images of the carrier cross section taken with a scanning electron microscope (ScanN iNg ElectroN Microscope, SEM) are imported into an image processing analyzer and subjected to image analysis. 100 inorganic particles (primary particles) in the resin coating layer are randomly selected, and the circle equivalent diameter (Nm) of each is calculated and the arithmetic average is calculated, which is the average particle diameter (Nm) of the inorganic particles.
[0089] The surface of the inorganic particles may be subjected to hydrophobic treatment. Examples of the hydrophobic treatment agent include known organosilicon compounds having an alkyl group (e.g., methyl group, ethyl group, propyl group, butyl group, etc.), and specific examples include alkoxysilane compounds, siloxane compounds, and silazane compounds. Among these, the hydrophobic treatment agent is preferably a silazane compound, and hexamethyldisilazane is preferable. The hydrophobic treatment agent may be used alone or in combination of two or more kinds.
[0090] Examples of methods for hydrophobizing inorganic particles with a hydrophobizing agent include a method in which supercritical carbon dioxide is used to dissolve the hydrophobizing agent in supercritical carbon dioxide and adhere the hydrophobizing agent to the surfaces of the inorganic particles; a method in which a solution containing a hydrophobizing agent and a solvent that dissolves the hydrophobizing agent is applied (e.g., sprayed or coated) to the surfaces of inorganic particles in the atmosphere to adhere the hydrophobizing agent to the surfaces of the inorganic particles; and a method in which a solution containing a hydrophobizing agent and a solvent that dissolves the hydrophobizing agent is added to an inorganic particle dispersion in the atmosphere, the solution is maintained, and then the mixed solution of the inorganic particle dispersion and the solution is dried.
[0091] From the viewpoint of suppressing concentration change, the content of inorganic particles contained in the resin coating layer is preferably 10% by mass or more and 60% by mass or less, more preferably 15% by mass or more and 55% by mass or less, and even more preferably 20% by mass or more and 50% by mass or less, relative to the total mass of the resin coating layer.
[0092] The solvent used in forming the coating resin layer is not particularly limited as long as it dissolves or disperses the resin. For example, aromatic hydrocarbons such as toluene and xylene; ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran and dioxane; etc. may be used. Of these, toluene is preferred.
[0093] The solid content of the mixed liquid used to form the coating resin layer is not particularly limited, but is preferably from 5% to 50% by mass, and more preferably from 10% to 30% by mass.
[0094] Furthermore, the mixed liquid may contain conductive particles or inorganic particles, and in Coating A, conductive particles or inorganic particles may be added separately from the mixed liquid.
[0095] The average thickness of the resin coating layer is preferably from 0.1 μm to 10 μm, more preferably from 0.2 μm to 5 μm, and even more preferably from 0.3 μm to 3 μm.
[0096] The average thickness of the resin coating layer is measured by the following method. The carrier is embedded in epoxy resin or the like, and cut with a diamond knife or the like to prepare a thin slice. This thin slice is observed with a transmission electron microscope (TEM) or the like, and cross-sectional images of multiple carrier particles are taken. The thickness of the resin coating layer is measured at 20 points from the cross-sectional images of the carrier particles, and the average value is used.
[0097] <Method of manufacturing electrostatic image developer> The method for producing an electrostatic image developer according to this embodiment includes the method for producing an electrostatic image developing carrier according to this embodiment. Specifically, the method for producing an electrostatic image developer according to this embodiment includes a method for producing a carrier for developing electrostatic images according to this embodiment, and a step of mixing the carrier for developing electrostatic images produced by the method for producing a carrier for developing electrostatic images according to this embodiment with a toner. The electrostatic image developer manufactured by the method for manufacturing an electrostatic image developer according to this embodiment is a two-component developer containing a toner and a carrier for developing an electrostatic image manufactured by the method for manufacturing a carrier for developing an electrostatic image according to this embodiment.
[0098] The mixture ratio (mass ratio) of the carrier to the toner in the developer is preferably from 100:1 to 100:30, more preferably from 100:3 to 100:20.
[0099] <Toner> The toner contains toner particles and, if necessary, an external additive. The toner particles are configured to contain, for example, a binder resin, and, if necessary, a colorant, a release agent, and other additives.
[0100] -Binding resin- Examples of the binder resin include vinyl resins made of homopolymers of monomers such as styrenes (e.g., styrene, parachlorostyrene, α-methylstyrene, etc.), (meth)acrylic acid esters (e.g., methyl acrylate, ethyl acrylate, N-propyl acrylate, N-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, N-propyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, etc.), ethylenically unsaturated nitriles (e.g., acrylonitrile, methacrylonitrile, etc.), vinyl ethers (e.g., vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketones (e.g., vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.), and olefins (e.g., ethylene, propylene, butadiene, etc.), or copolymers of two or more of these monomers. Examples of the binder resin include non-vinyl resins such as epoxy resins, polyester resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, and modified rosin, mixtures of these with the vinyl resins, and graft polymers obtained by polymerizing vinyl monomers in the coexistence of these. These binder resins may be used alone or in combination of two or more kinds.
[0101] The binder resin is preferably a polyester resin. The polyester resin may be, for example, a known amorphous polyester resin. The polyester resin may be used in combination with a crystalline polyester resin together with the amorphous polyester resin. However, the content of the crystalline polyester resin is preferably in the range of 2% by mass to 40% by mass (preferably 2% by mass to 20% by mass) based on the total binder resin.
[0102] The "crystallinity" of a resin refers to the presence of a clear endothermic peak rather than a stepwise change in the amount of endothermic heat in differential scanning calorimetry (DSC); specifically, it refers to the half-width of the endothermic peak being within 10°C when measured at a heating rate of 10 (°C / min). On the other hand, the term "amorphous" for a resin refers to a half-width exceeding 10° C., a stepwise change in endothermic heat quantity, or no clear endothermic peak being observed.
[0103] Amorphous polyester resin The amorphous polyester resin may be, for example, a condensation polymer of a polyvalent carboxylic acid and a polyhydric alcohol. As the amorphous polyester resin, a commercially available product or a synthesized product may be used.
[0104] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenylsuccinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (e.g., cyclohexanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). Among these, aromatic dicarboxylic acids are preferable as polyvalent carboxylic acids. The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, anhydrides thereof, and lower (e.g., carbon number 1 to 5) alkyl esters thereof. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.
[0105] Examples of polyhydric alcohols include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among these, examples of polyhydric alcohols include aromatic diols and alicyclic diols, and more preferably aromatic diols. As the polyhydric alcohol, a polyhydric alcohol having a crosslinked or branched structure of three or more may be used in combination with the diol. Examples of the polyhydric alcohol having a trihydric or higher valence include glycerin, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.
[0106] The glass transition temperature (Tg) of the amorphous polyester resin is preferably 50°C or higher and 80°C or lower, and more preferably 50°C or higher and 65°C or lower. The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), and more specifically, it is determined from the "extrapolated glass transition onset temperature" described in the method for determining glass transition temperature in JIS K7121:1987 "Method for measuring transition temperature of plastics."
[0107] The weight average molecular weight (Mw) of the amorphous polyester resin is preferably 5,000 or more and 1,000,000 or less, and more preferably 7,000 or more and 500,000 or less. The number average molecular weight (MN) of the amorphous polyester resin is preferably 2,000 or more and 100,000 or less. The molecular weight distribution Mw / MN of the amorphous polyester resin is preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less. The weight average molecular weight and number average molecular weight are measured by gel permeation chromatography (GPC). The molecular weight measurement by GPC is performed using a Tosoh GPC HLC-8120GPC as the measuring device, a Tosoh TSKgel SuperHM-M (15 cm) column, and THF solvent. The weight average molecular weight and number average molecular weight are calculated from the measurement results using a molecular weight calibration curve created with a monodisperse polystyrene standard sample.
[0108] The amorphous polyester resin can be obtained by a known production method, for example, by carrying out the reaction while removing water and alcohol generated during condensation by setting the polymerization temperature to 180° C. or higher and 230° C. or lower, and reducing the pressure in the reaction system as necessary. If the raw material monomer is not soluble or compatible at the reaction temperature, a high boiling point solvent may be added as a solubilizing agent to dissolve it. In this case, the polycondensation reaction is carried out while distilling off the solubilizing agent. If a monomer with poor compatibility is present in the copolymerization reaction, it is recommended that the monomer with poor compatibility is condensed in advance with the acid or alcohol to be polycondensed, and then polycondensed with the main component.
[0109] Crystalline polyester resin The crystalline polyester resin may be, for example, a polycondensate of a polyvalent carboxylic acid and a polyhydric alcohol. As the crystalline polyester resin, a commercially available product or a synthesized product may be used. Here, the crystalline polyester resin is preferably a polycondensate using a straight-chain aliphatic polymerizable monomer rather than a polymerizable monomer having an aromatic ring, since it easily forms a crystalline structure.
[0110] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent carboxylic acid include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, and their lower alkyl esters (e.g., carbon number 1 to 5). As the polybasic carboxylic acid, a dicarboxylic acid having a sulfonic acid group and a dicarboxylic acid having an ethylenic double bond may be used in combination with these dicarboxylic acids. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.
[0111] Examples of polyhydric alcohols include aliphatic diols (for example, straight-chain aliphatic diols having 7 to 20 carbon atoms in the main chain). Examples of aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosanedecanediol. Among these, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol are preferred as aliphatic diols. The polyhydric alcohol may be a trihydric or higher alcohol having a crosslinked or branched structure in combination with the diol. Examples of the trihydric or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.
[0112] Here, the polyhydric alcohol has an aliphatic diol content of 80 mol % or more, preferably 90 mol % or more.
[0113] The melting temperature of the crystalline polyester resin is preferably 50°C or higher and 100°C or lower, more preferably 55°C or higher and 90°C or lower, and even more preferably 60°C or higher and 85°C or lower. The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "peak melting temperature" described in the method for determining melting temperature in JIS K7121:1987 "Method for measuring transition temperature of plastics."
[0114] The weight average molecular weight (Mw) of the crystalline polyester resin is preferably 6,000 or more and 35,000 or less.
[0115] The crystalline polyester resin can be obtained, for example, by a known production method, like the amorphous polyester.
[0116] The content of the binder resin is preferably from 40% by mass to 95% by mass, more preferably from 50% by mass to 90% by mass, and even more preferably from 60% by mass to 85% by mass, based on the total mass of the toner particles.
[0117] -Coloring agent- Examples of colorants include carbon black, chrome yellow, Hansa Yellow, benzidine yellow, threne yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, Balkan orange, watch young red, permanent red, brilliant carmine 3B, brilliant carmine 6B, DuPont oil red, pyrazolone red, lithol red, rhodamine B lake, lake red C, pigment red, rose bengal, aniline blue, Examples of the dyes include pigments such as ultramarine blue, chalcoil blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, and malachite green oxalate; and dyes such as acridine-based, xanthene-based, azo-based, benzoquinone-based, azine-based, anthraquinone-based, thioindigo-based, dioxazine-based, thiazine-based, azomethine-based, indigo-based, phthalocyanine-based, aniline black-based, polymethine-based, triphenylmethane-based, diphenylmethane-based, and thiazole-based dyes. The colorant may be used alone or in combination of two or more kinds.
[0118] The colorant may be surface-treated as necessary, or may be used in combination with a dispersant. In addition, a plurality of types of colorants may be used in combination.
[0119] The content of the colorant is preferably from 1% by mass to 30% by mass, and more preferably from 3% by mass to 15% by mass, based on the total mass of the toner particles.
[0120] -Release agent- Examples of the release agent include hydrocarbon waxes, natural waxes such as carnauba wax, rice wax, and candelilla wax, synthetic or mineral / petroleum waxes such as montan wax, and ester waxes such as fatty acid esters and montan acid esters. The release agent is not limited to these.
[0121] The melting temperature of the release agent is preferably 50°C or higher and 110°C or lower, and more preferably 60°C or higher and 100°C or lower. The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "peak melting temperature" described in the method for determining melting temperature in JIS K7121:1987 "Method for measuring transition temperature of plastics."
[0122] The content of the release agent is preferably from 1% by mass to 20% by mass, and more preferably from 5% by mass to 15% by mass, based on the total mass of the toner particles.
[0123] -Other additives- Examples of other additives include known additives such as magnetic materials, charge control agents, inorganic powders, etc. These additives are contained in the toner particles as internal additives.
[0124] -Characteristics of toner particles, etc.- The toner particles may be toner particles having a single layer structure, or may be toner particles having a so-called core-shell structure composed of a core portion (core particle) and a coating layer (shell layer) that coats the core portion. The toner particles having a core-shell structure may be composed of, for example, a core containing a binder resin and, if necessary, other additives such as a colorant and a release agent, and a coating layer containing the binder resin.
[0125] The volume average particle size (D50v) of the toner particles is preferably from 2 μm to 10 μm, and more preferably from 4 μm to 8 μm. The volume average particle size (D50v) of the toner particles is measured using a Coulter Multisizer II (manufactured by Beckman Coulter, Inc.), and the electrolyte is measured using an ISOTON-II (manufactured by Beckman Coulter, Inc.). For the measurement, 0.5 mg to 50 mg of the measurement sample is added to 2 ml of a 5 mass % aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate) as a dispersant, and this is then added to 100 ml to 150 ml of the electrolyte. The electrolyte with the sample suspended in it is dispersed for 1 minute using an ultrasonic disperser, and the particle size distribution of particles with diameters in the range of 2 μm to 60 μm is measured using a Coulter Multisizer II with an aperture diameter of 100 μm. The number of particles sampled is 50,000. The particle size distribution based on volume is plotted from the smallest diameter side, and the particle size at which the cumulative 50% is reached is defined as the volume average particle size D50v.
[0126] The average circularity of the toner particles is preferably 0.94 or more and 1.00 or less, and more preferably 0.95 or more and 0.98 or less. The average circularity of toner particles is calculated by (circular equivalent perimeter) / (perimeter) [(perimeter of a circle having the same projected area as the particle image) / (perimeter of the particle projected image)]. Specifically, it is a value measured by the following method. First, the toner particles to be measured are sucked and collected, flattened, and a still image of the particles is captured by instantaneous strobe light emission, and the particle image is analyzed by a flow-type particle image analyzer (FPIA-3000 manufactured by Sysmex Corporation). The number of samples to be taken in order to calculate the average circularity is 3,500. When the toner contains an external additive, the toner (developer) to be measured is dispersed in water containing a surfactant, and then ultrasonic treatment is performed to obtain toner particles from which the external additive has been removed.
[0127] -Method of manufacturing toner particles- The toner particles may be produced by any of a dry production method (e.g., a kneading and pulverizing method, etc.) and a wet production method (e.g., an aggregation and coalescence method, a suspension polymerization method, a dissolution suspension method, etc.). There is no particular limitation on these production methods, and any known production method may be used. Among these, it is preferable to obtain the toner particles by the aggregation and coalescence method.
[0128] Specifically, for example, when toner particles are produced by the aggregation and coalescence method, the toner particles are produced through a step of preparing a resin particle dispersion in which resin particles to be a binder resin are dispersed (resin particle dispersion preparation step), a step of aggregating resin particles (other particles, if necessary) in the resin particle dispersion (in a dispersion after mixing other particle dispersions, if necessary) to form aggregated particles (aggregated particle formation step), and a step of heating the aggregated particle dispersion in which the aggregated particles are dispersed, to fuse and coalesce the aggregated particles, thereby forming toner particles (fusion and coalescence step).
[0129] Each step will be described in detail below. In the following description, a method for obtaining toner particles containing a colorant and a release agent will be described, but the colorant and the release agent are used as necessary. Of course, additives other than the colorant and the release agent may be used.
[0130] -Resin particle dispersion preparation process- Along with a resin particle dispersion in which resin particles serving as a binder resin are dispersed, for example, a colorant particle dispersion in which colorant particles are dispersed, and a release agent particle dispersion in which release agent particles are dispersed are prepared.
[0131] The resin particle dispersion liquid is prepared, for example, by dispersing resin particles in a dispersion medium with the aid of a surfactant.
[0132] The dispersion medium used in the resin particle dispersion liquid is, for example, an aqueous medium. Examples of the aqueous medium include water such as distilled water and ion-exchanged water, alcohols, etc. These may be used alone or in combination of two or more.
[0133] Examples of the surfactant include anionic surfactants such as sulfate salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols. Among these, anionic surfactants and cationic surfactants are particularly preferred. The nonionic surfactants may be used in combination with anionic surfactants or cationic surfactants. The surfactant may be used alone or in combination of two or more kinds.
[0134] In the resin particle dispersion, the resin particles are dispersed in the dispersion medium by a general dispersion method such as a rotary shear type homogenizer, a ball mill having a media, a sand mill, or a dyno mill. Depending on the type of resin particles, the resin particles may be dispersed in the dispersion medium by a phase inversion emulsification method. The phase inversion emulsification method is a method in which the resin to be dispersed is dissolved in a hydrophobic organic solvent in which the resin is soluble, a base is added to the organic continuous phase (O phase) to neutralize it, and then an aqueous medium (W phase) is added to invert the phase from W / O to O / W, thereby dispersing the resin in the aqueous medium in the form of particles.
[0135] The volume average particle size of the resin particles dispersed in the resin particle dispersion is, for example, preferably from 0.01 μm to 1 μm, more preferably from 0.08 μm to 0.8 μm, and even more preferably from 0.1 μm to 0.6 μm. The volume average particle size of the resin particles is measured by using a particle size distribution obtained by measurement using a laser diffraction particle size distribution measuring device (for example, LA-700 manufactured by Horiba, Ltd.), subtracting the cumulative distribution from the small particle size side for the volume of the divided particle size range (channel), and measuring the particle size at which the cumulative distribution is 50% of all particles as the volume average particle size D50v. The volume average particle sizes of particles in other dispersions are measured in the same manner.
[0136] The content of the resin particles in the resin particle dispersion is preferably from 5% by mass to 50% by mass, and more preferably from 10% by mass to 40% by mass.
[0137] In the same manner as the resin particle dispersion liquid, for example, a colorant particle dispersion liquid and a release agent particle dispersion liquid are also prepared. That is, the volume average particle size, dispersion medium, dispersion method, and particle content of the particles in the resin particle dispersion liquid are the same for the colorant particles dispersed in the colorant particle dispersion liquid and the release agent particles dispersed in the release agent particle dispersion liquid.
[0138] -Agglomerated particle formation process- Next, the resin particle dispersion liquid, the colorant particle dispersion liquid, and the release agent particle dispersion liquid are mixed together. Then, in the mixed dispersion, the resin particles, the colorant particles, and the release agent particles are hetero-aggregated to form aggregated particles containing the resin particles, the colorant particles, and the release agent particles and having a diameter close to that of the target toner particles.
[0139] Specifically, for example, an aggregating agent is added to the mixed dispersion, the pH of the mixed dispersion is adjusted to be acidic (e.g., pH 2 or more and 5 or less), a dispersion stabilizer is added as necessary, and then the mixed dispersion is heated to a temperature close to the glass transition temperature of the resin particles (specifically, for example, glass transition temperature of the resin particles -30°C or more and glass transition temperature -10°C or less), and the particles dispersed in the mixed dispersion are aggregated to form aggregated particles. In the aggregated particle formation process, for example, the mixed dispersion may be stirred with a rotary shear homogenizer, an aggregating agent may be added at room temperature (e.g., 25°C), the pH of the mixed dispersion may be adjusted to an acidic state (e.g., pH 2 or more and 5 or less), a dispersion stabilizer may be added as necessary, and then the mixture may be heated.
[0140] Examples of the flocculant include a surfactant having a polarity opposite to that of the surfactant contained in the mixed dispersion, an inorganic metal salt, and a divalent or higher metal complex. When a metal complex is used as the flocculant, the amount of the surfactant used is reduced, and the charging characteristics are improved. If necessary, an additive that forms a complex or a similar bond with the metal ion of the flocculant may be used together with the flocculant. As this additive, a chelating agent is preferably used.
[0141] Examples of inorganic metal salts include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate; and inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide. The chelating agent may be a water-soluble chelating agent, for example, oxycarboxylic acid such as tartaric acid, citric acid, gluconic acid, etc., aminocarboxylic acid such as iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), ethylenediaminetetraacetic acid (EDTA), etc. The amount of the chelating agent added is preferably from 0.01 to 5.0 parts by mass, and more preferably from 0.1 to less than 3.0 parts by mass, relative to 100 parts by mass of the resin particles.
[0142] -Fusion / unification process- Next, the aggregated particle dispersion liquid in which the aggregated particles are dispersed is heated, for example, to a temperature equal to or higher than the glass transition temperature of the resin particles (for example, a temperature 10° C. to 30° C. higher than the glass transition temperature of the resin particles) to fuse and coalesce the aggregated particles to form toner particles.
[0143] Through the above steps, toner particles are obtained. After obtaining the aggregated particle dispersion in which the aggregated particles are dispersed, the aggregated particle dispersion and the resin particle dispersion in which the resin particles are dispersed are further mixed together to aggregate the aggregated particles so that the resin particles are further attached to the surfaces of the aggregated particles, thereby forming second aggregated particles; and the second aggregated particle dispersion in which the second aggregated particles are dispersed is heated to fuse and coalesce the second aggregated particles, thereby forming toner particles having a core-shell structure.
[0144] After the fusion and coalescence process is completed, the toner particles formed in the solution are subjected to a known washing process, solid-liquid separation process, and drying process to obtain dried toner particles. From the viewpoint of chargeability, the washing process is preferably performed by sufficient substitution washing with ion-exchanged water. From the viewpoint of productivity, the solid-liquid separation process is preferably performed by suction filtration, pressure filtration, etc. From the viewpoint of productivity, the drying process is preferably performed by freeze drying, air flow drying, fluidized drying, vibration type fluidized drying, etc.
[0145] The toner used in the present embodiment is produced, for example, by adding an external additive to the obtained toner particles in a dry state and mixing them. The mixing may be performed, for example, by using a V blender, a Henschel mixer, a Loedige mixer, etc. Furthermore, if necessary, coarse particles of the toner may be removed using a vibration sieve, an air sieve, etc.
[0146] -External additives- Examples of the external additive include inorganic particles. Examples of the inorganic particles include SiO2, TiO2, Al2O3, CuO, ZNO, SNO2, CeO2, Fe2O3, MgO, BaO, CaO, K2O, Na2O, ZrO2, CaO·SiO2, and K2O·(TiO2). N , Al2O3·2SiO2, CaCO3, MgCO3, BaSO4, MgSO4, etc.
[0147] The surface of the inorganic particles as an external additive may be subjected to a hydrophobic treatment. The hydrophobic treatment may be performed, for example, by immersing the inorganic particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and examples thereof include silane coupling agents, silicone oils, titanate coupling agents, and aluminum coupling agents. These may be used alone or in combination of two or more. The amount of the hydrophobizing agent is usually, for example, 1 part by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the inorganic particles.
[0148] Examples of external additives include resin particles (resin particles such as polystyrene, polymethyl methacrylate, and melamine resin), cleaning agents (for example, metal salts of higher fatty acids such as zinc stearate, and fluorine-based polymer particles), and the like.
[0149] The amount of the external additive is preferably from 0.01% by mass to 5% by mass, and more preferably from 0.01% by mass to 2.0% by mass, based on the toner particles.
[0150] ≪Image forming apparatus, image forming method≫ The above-described electrostatic image developer, i.e., the electrostatic image developer containing the electrostatic image developing carrier manufactured by the manufacturing method of the electrostatic image developing carrier according to the present embodiment, is applied to the image forming apparatus and image forming method described below. The image forming apparatus used in this embodiment includes an image carrier, a charging means for charging the surface of the image carrier, an electrostatic image forming means for forming an electrostatic image on the charged surface of the image carrier, a developing means for containing an electrostatic image developer and developing the electrostatic image formed on the surface of the image carrier as a toner image using the electrostatic image developer, a transfer means for transferring the toner image formed on the surface of the image carrier to the surface of a recording medium, and a fixing means for fixing the toner image transferred to the surface of the recording medium.
[0151] The image forming apparatus used in this embodiment carries out an image forming method including a charging step of charging the surface of an image carrier, an electrostatic image forming step of forming an electrostatic image on the charged surface of the image carrier, a developing step of developing the electrostatic image formed on the surface of the image carrier as a toner image using the electrostatic image developer according to this embodiment, a transfer step of transferring the toner image formed on the surface of the image carrier to the surface of a recording medium, and a fixing step of fixing the toner image transferred to the surface of the recording medium.
[0152] The image forming apparatus used in this embodiment may be a known image forming apparatus such as a direct transfer type apparatus that directly transfers a toner image formed on the surface of an image holder to a recording medium; an intermediate transfer type apparatus that primarily transfers a toner image formed on the surface of an image holder to the surface of an intermediate transfer body, and then secondarily transfers the toner image transferred to the surface of the intermediate transfer body to the surface of a recording medium; an apparatus equipped with a cleaning means that cleans the surface of the image holder after the transfer of the toner image and before charging; or an apparatus equipped with a discharging means that irradiates the surface of the image holder with discharging light to discharge it after the transfer of the toner image and before charging it. When the image forming apparatus used in the present embodiment is an intermediate transfer type apparatus, the transfer means is configured to have, for example, an intermediate transfer body onto whose surface a toner image is transferred, a primary transfer means which primarily transfers the toner image formed on the surface of the image carrier onto the surface of the intermediate transfer body, and a secondary transfer means which secondarily transfers the toner image transferred onto the surface of the intermediate transfer body onto the surface of a recording medium.
[0153] In the image forming apparatus used in the present embodiment, for example, a portion including the developing means may have a cartridge structure (process cartridge) that is detachably attached to the image forming apparatus. As the process cartridge, for example, a process cartridge that contains an electrostatic image developer including the electrostatic image developing carrier manufactured by the manufacturing method for the electrostatic image developing carrier according to the present embodiment and has a developing means is preferably used.
[0154] An example of an image forming apparatus used in the present embodiment will be described below, but the present invention is not limited to this example. In the following description, the main parts shown in the drawings will be described, and the description of the rest will be omitted.
[0155] FIG. 1 is a schematic diagram showing the configuration of an image forming apparatus used in this embodiment. The image forming apparatus shown in Fig. 1 includes first to fourth image forming units 10Y, 10M, 10C, and 10K (image forming means) of an electrophotographic type that output images of each color of yellow (Y), magenta (M), cyan (C), and black (K) based on color-separated image data. These image forming units (hereinafter sometimes simply referred to as "units") 10Y, 10M, 10C, and 10K are arranged in parallel at predetermined distances from each other in the horizontal direction. These units 10Y, 10M, 10C, and 10K may be process cartridges that are detachably attached to the image forming apparatus.
[0156] Above each of the units 10Y, 10M, 10C, and 10K, an intermediate transfer belt (one example of an intermediate transfer body) 20 is provided, which extends through each unit. The intermediate transfer belt 20 is provided wrapped around a drive roll 22 and a support roll 24, and runs in a direction from the first unit 10Y toward the fourth unit 10K. A force is applied to the support roll 24 by a spring (not shown) or the like in a direction away from the drive roll 22, and tension is applied to the intermediate transfer belt 20 wrapped around them. An intermediate transfer body cleaning device 30 is provided on the image carrier side of the intermediate transfer belt 20, facing the drive roll 22. The developing devices (an example of developing means) 4Y, 4M, 4C, and 4K of the units 10Y, 10M, 10C, and 10K are supplied with yellow, magenta, cyan, and black toners contained in toner cartridges 8Y, 8M, 8C, and 8K, respectively.
[0157] Since the first to fourth units 10Y, 10M, 10C, and 10K have the same configuration and operation, the first unit 10Y that forms a yellow image and is disposed upstream in the direction in which the intermediate transfer belt travels will be described here as a representative.
[0158] The first unit 10Y has a photoconductor 1Y that acts as an image carrier. Around the photoconductor 1Y, a charging roll (an example of a charging means) 2Y that charges the surface of the photoconductor 1Y to a predetermined potential, an exposure device (an example of an electrostatic image forming means) 3 that exposes the charged surface to a laser beam 3Y based on a color-separated image signal to form an electrostatic image, a developing device (an example of a developing means) 4Y that supplies charged toner to the electrostatic image to develop it, a primary transfer roll 5Y (an example of a primary transfer means) that transfers the developed toner image onto an intermediate transfer belt 20, and a photoconductor cleaning device (an example of a cleaning means) 6Y that removes toner remaining on the surface of the photoconductor 1Y after the primary transfer are arranged in this order. The primary transfer roll 5Y is disposed inside the intermediate transfer belt 20, and is provided at a position facing the photoconductor 1Y. A bias power supply (not shown) that applies a primary transfer bias is connected to the primary transfer rolls 5Y, 5M, 5C, and 5K of each unit. Each bias power supply changes the value of the transfer bias applied to each primary transfer roll under the control of a control unit (not shown).
[0159] Hereinafter, the operation of forming a yellow image in the first unit 10Y will be described. First, prior to operation, the surface of the photoconductor 1Y is charged to a potential of −600V to −800V by the charging roll 2Y. The photoconductor 1Y has a conductivity (for example, a volume resistivity of 1×10 at 20° C. -6 The photosensitive layer is formed by laminating a photosensitive layer on a substrate having a resistivity of Ωcm or less. This photosensitive layer is usually highly resistive (the resistance of ordinary resins), but when irradiated with a laser beam, the resistivity of the portion irradiated with the laser beam changes. Therefore, the exposed surface of the charged photoreceptor 1Y is irradiated with a laser beam 3Y from the exposure device 3 in accordance with image data for yellow sent from a control unit (not shown). As a result, an electrostatic charge image of a yellow image pattern is formed on the surface of the photoreceptor 1Y.
[0160] An electrostatic image is an image formed on the surface of the photoconductor 1Y by electrostatic charging. The laser beam 3Y reduces the resistivity of the irradiated parts of the photosensitive layer, causing the charged charges on the surface of the photoconductor 1Y to flow, while the charges remain in the parts not irradiated by the laser beam 3Y. This is a so-called negative latent image. The electrostatic image formed on the photoconductor 1Y rotates to a predetermined developing position as the photoconductor 1Y travels. At this developing position, the electrostatic image on the photoconductor 1Y is developed into a toner image by the developing device 4Y and made visible.
[0161] The developing device 4Y contains an electrostatic image developer including at least yellow toner and a carrier, for example. The yellow toner is triboelectrically charged by being stirred inside the developing device 4Y, and is held on a developer roll (an example of a developer holder) with a charge of the same polarity (negative polarity) as the charge on the photoconductor 1Y. As the surface of the photoconductor 1Y passes through the developing device 4Y, the yellow toner electrostatically adheres to the discharged latent image portion on the surface of the photoconductor 1Y, and the latent image is developed with the yellow toner. The photoconductor 1Y on which the yellow toner image has been formed continues to travel at a predetermined speed, and the toner image developed on the photoconductor 1Y is transported to a predetermined primary transfer position.
[0162] When the yellow toner image on the photoreceptor 1Y is transported to the primary transfer position, a primary transfer bias is applied to the primary transfer roll 5Y, and an electrostatic force from the photoreceptor 1Y toward the primary transfer roll 5Y acts on the toner image, and the toner image on the photoreceptor 1Y is transferred onto the intermediate transfer belt 20. The transfer bias applied at this time has a polarity (+) opposite to the polarity (-) of the toner, and is controlled to, for example, +10 μA by a control unit (not shown) in the first unit 10Y. On the other hand, the toner remaining on the photoconductor 1Y is removed and collected by the photoconductor cleaning device 6Y.
[0163] The primary transfer bias applied to the primary transfer rolls 5M, 5C, and 5K subsequent to the second unit 10M is also controlled in accordance with the first unit. In this manner, the intermediate transfer belt 20 onto which the yellow toner image has been transferred by the first unit 10Y is conveyed successively through the second to fourth units 10M, 10C, and 10K, where the toner images of each color are transferred and superimposed.
[0164] The intermediate transfer belt 20 onto which the four color toner images have been transferred in multiple layers through the first to fourth units reaches a secondary transfer section that is composed of the intermediate transfer belt 20, a support roll 24 that contacts the inner surface of the intermediate transfer belt, and a secondary transfer roll (an example of a secondary transfer means) 26 arranged on the image bearing surface side of the intermediate transfer belt 20. Meanwhile, a recording paper (an example of a recording medium) P is fed at a predetermined timing into the gap between the secondary transfer roll 26 and the intermediate transfer belt 20 via a supply mechanism, and a secondary transfer bias is applied to the support roll 24. The transfer bias applied at this time has a (-) polarity that is the same as the (-) polarity of the toner, and an electrostatic force from the intermediate transfer belt 20 toward the recording paper P acts on the toner image, and the toner image on the intermediate transfer belt 20 is transferred onto the recording paper P. The secondary transfer bias at this time is determined according to the resistance detected by a resistance detection means (not shown) that detects the resistance of the secondary transfer section, and is voltage-controlled.
[0165] Thereafter, the recording paper P is sent to a pressure contact portion (nip portion) of a pair of fixing rolls in a fixing device (one example of a fixing means) 28, where the toner image is fixed onto the recording paper P, forming a fixed image.
[0166] The recording paper P onto which the toner image is transferred can be, for example, plain paper used in electrophotographic copying machines, printers, etc. In addition to the recording paper P, other examples of the recording medium include overhead projector sheets and the like. To further improve the smoothness of the image surface after fixing, it is preferable that the surface of the recording paper P is also smooth. For example, coated paper in which the surface of ordinary paper is coated with resin or the like, art paper for printing, etc. are preferably used.
[0167] After the color image has been fixed, the recording paper P is conveyed toward the discharge section, and the series of color image forming operations is completed.
[0168] The electrostatic image developer containing the electrostatic image developing carrier produced by the method for producing the electrostatic image developing carrier according to this embodiment may be applied to a process cartridge. The process cartridge used in this embodiment is a process cartridge that contains an electrostatic image developer containing an electrostatic image developing carrier manufactured by the manufacturing method of an electrostatic image developing carrier according to this embodiment, and is equipped with a developing means that develops an electrostatic image formed on the surface of an image carrier into a toner image by the electrostatic image developer, and is detachably attached to an image forming apparatus.
[0169] The process cartridge used in the present embodiment is not limited to the above configuration, and may be configured to include a developing means and, as necessary, at least one other means selected from, for example, an image carrier, a charging means, an electrostatic image forming means, and a transfer means.
[0170] An example of a process cartridge used in the present embodiment will be described below, but the present invention is not limited to this example. In the following description, the main parts shown in the drawings will be described, and the description of the rest will be omitted.
[0171] FIG. 2 is a schematic diagram showing the configuration of a process cartridge used in this embodiment. The process cartridge 200 shown in FIG. 2 is configured by, for example, a housing 117 having a mounting rail 116 and an opening 118 for exposure, and integrally combining and holding a photoconductor 107 (an example of an image carrier), a charging roll 108 (an example of a charging means) provided around the photoconductor 107, a developing device 111 (an example of a developing means), and a photoconductor cleaning device 113 (an example of a cleaning means), which are assembled into a cartridge. In FIG. 2, 109 indicates an exposure device (an example of an electrostatic image forming means), 112 indicates a transfer device (an example of a transfer means), 115 indicates a fixing device (an example of a fixing means), and 300 indicates a recording paper (an example of a recording medium). EXAMPLES
[0172] Hereinafter, the embodiments of the present invention will be described in detail with reference to examples, but the embodiments of the present invention are not limited to these examples. In the following description, unless otherwise specified, "parts" and "%" are based on mass.
[0173] <Toner Production> (Preparation of amorphous polyester resin dispersion (A1)) Ethylene glycol: 37 parts Neopentyl glycol: 65 parts 1,9-nonanediol: 32 parts Terephthalic acid: 96 parts The above materials were charged in a flask, and the temperature was raised to 200°C over 1 hour. After confirming that the reaction system was stirred uniformly, 1.2 parts of dibutyltin oxide were added. The temperature was raised to 240°C over 6 hours while distilling off the water produced, and stirring was continued at 240°C for 4 hours to obtain an amorphous polyester resin (acid value 9.4 mgKOH / g, weight average molecular weight 13,000, glass transition temperature 62°C). The amorphous polyester resin was transferred to an emulsifier / disperser (Cavitron CD1010, Eurotech) in a molten state at a rate of 100 g per minute. Separately, a dilute ammonia water with a concentration of 0.37% obtained by diluting reagent ammonia water with ion-exchanged water was placed in a tank, and the dilute ammonia water was transferred to the emulsifier / disperser at a rate of 0.1 liters per minute simultaneously with the amorphous polyester resin while being heated to 120°C with a heat exchanger. The emulsifier / disperser was operated at a rotor rotation speed of 60Hz and a pressure of 5kg / cm. 2 By operating under the above conditions, a non-crystalline polyester resin dispersion (A1) having a volume average particle size of 160 nm and a solid content of 20% was obtained.
[0174] [Preparation of crystalline polyester resin dispersion (C1)] Decanedioic acid: 81 parts Hexanediol: 47 parts The above materials were charged into a flask, and the temperature was raised to 160°C over 1 hour. After confirming that the reaction system was stirred uniformly, 0.03 parts of dibutyltin oxide was added. The temperature was raised to 200°C over 6 hours while distilling off the water produced, and stirring was continued at 200°C for 4 hours. The reaction liquid was then cooled, solid-liquid separation was performed, and the solid matter was dried at a temperature of 40°C under reduced pressure to obtain a crystalline polyester resin (C1) (melting point 64°C, weight average molecular weight 15,000).
[0175] Crystalline polyester resin (C1): 50 parts Anionic surfactant (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Neogen RK): 2 parts -Ion-exchanged water: 200 parts The above materials were heated to 120°C, thoroughly dispersed using a homogenizer (Ultra Turrax T50, IKA), and then dispersed using a pressure discharge homogenizer. When the volume average particle size reached 180 nm, the particles were collected to obtain a crystalline polyester resin dispersion (C1) with a solid content of 20%.
[0176] [Preparation of release agent particle dispersion (W1)] Paraffin wax (HNP-9, manufactured by Nippon Seiro Co., Ltd.): 100 parts Anionic surfactant (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Neogen RK): 1 part Ion-exchanged water: 350 parts The above materials were mixed and heated to 100°C, dispersed using a homogenizer (IKA Ultra Turrax T50), and then dispersed using a pressure discharge Gaulin homogenizer to obtain a release agent particle dispersion in which release agent particles with a volume average particle size of 200 nm were dispersed. Ion-exchanged water was added to this release agent particle dispersion to adjust the solid content to 20%, and this was used as release agent particle dispersion (W1).
[0177] [Preparation of colorant particle dispersion (Y1)] Yellow pigment (CI Pigment Yellow 180): 50 parts Anionic surfactant (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., Neogen RK): 5 parts Ion-exchanged water: 195 parts The above materials were mixed and dispersed for 60 minutes using a high-pressure impact disperser (Ultimaizer HJP30006, Sugino Machine Co., Ltd.) to obtain a colorant particle dispersion (K1) with a solid content of 20%.
[0178] [Preparation of Yellow Toner Particles (Y1)] -Ion-exchanged water: 200 parts Amorphous polyester resin dispersion (A1): 150 parts Crystalline polyester resin dispersion (C1): 10 parts Release agent particle dispersion (W1): 10 parts Colorant particle dispersion (Y1): 15 parts Anionic surfactant (TaycaPower): 2.8 parts The above materials were placed in a round stainless steel flask, and 0.1N nitric acid was added to adjust the pH to 3.5, and then an aqueous solution of polyaluminum chloride in which 2 parts of polyaluminum chloride (Oji Paper Co., Ltd., 30% powder product) were dissolved in 30 parts of ion-exchanged water was added. After dispersion at 30°C using a homogenizer (IKA Ultra Turrax T50), the mixture was heated to 45°C in a heating oil bath and held until the volume average particle size became 4.9 μm. Next, 60 parts of amorphous polyester resin dispersion (A1) was added and held for 30 minutes. Next, when the volume average particle size became 5.2 μm, 60 parts of amorphous polyester resin dispersion (A1) was further added and held for 30 minutes. Next, 20 parts of a 10% NTA (nitrilotriacetic acid) metal salt aqueous solution (Chilest 70, Chelest Co., Ltd.) was added, and a 1N aqueous solution of sodium hydroxide was added to adjust the pH to 9.0. Next, 1 part of anionic surfactant (TaycaPower) was added, and the mixture was heated to 85° C. while continuing to stir, and maintained at that temperature for 5 hours. The mixture was then cooled to 20° C. at a rate of 20° C. / min. The mixture was then filtered, thoroughly washed with ion-exchanged water, and dried to obtain yellow toner particles (Y1) having a volume average particle size of 5.7 μm and an average circularity of 0.971.
[0179] Next, silica (SiO2) particles with an average primary particle size of 40 nm that had been surface-hydrophobized with hexamethyldisilazane (hereinafter sometimes abbreviated as "HMDS") and metatitanic acid compound particles with an average primary particle size of 20 nm, which are the reaction product of metatitanic acid and isobutyltrimethoxysilane, were added to the yellow toner particles (Y1) so that the coverage rate of the toner particle surface was 40%, and mixed in a Henschel mixer to produce yellow toner (Y1).
[0180] [Preparation of Mixture 1] Lacquer (a solution of 20 parts of polycyclohexyl methacrylate (weight average molecular weight: 68,000, glass transition temperature Tg: 110°C) mixed with 80 parts of toluene): 100 parts Carbon black (average particle size 0.2 μm): 0.2 parts The above materials were charged into a sand mill and dispersed for 30 minutes, and then mixed solution 1 was obtained.
[0181] Example 1 Ferrite core (volume average particle size 35 μm): 100 parts Mixture 1: Amount that gives a resin solid content of 3.0 parts per 100 parts of ferrite core The above components were put into a batch-type stirring vacuum mixer (Inoue Manufacturing Co., Ltd. 50L kneader, stirring blade diameter D = 0.25m, clearance between the blade outer circumference and the casing inner wall / D = 3.5%) with the jacket temperature warmed to 90 ° C., and preheated (heated) to 70 ° C. while stirring and mixing at 60 rpm. Next, the internal pressure of the mixer was reduced to 5 kPa-abs, and this was continued until the load power value of the stirring blade before drying of the solvent increased as the drying progressed, and the drying was completed and the load power value decreased to 1.3 times or less the value before drying, forming a resin coating layer on the surface of the magnetic particles to obtain resin-coated magnetic particles. At this time, the temperature of the obtained resin-coated magnetic particles had risen to 98 ° C. Next, the resin-coated magnetic particles were crushed in the mixer for 30 minutes while maintaining the resin-coated magnetic particles at 100 ° C. The crushing conditions for the resin-coated magnetic particles are summarized in Table 1. Next, the stirring of the mixer was stopped, and the crushed resin-coated magnetic particles were directly fed from the mixer into a fluidized bed apparatus (Okawara Manufacturing, Slit Flow). In the fluidized bed apparatus, a fluidizing gas heated to 100°C was discharged at a superficial velocity of 20mm / s (twice the minimum fluidizing velocity Umf), and the resin-coated magnetic particles were fluidized for 60 minutes while maintaining the temperature at 100°C. Next, a fluidizing gas at 20°C was discharged at a superficial velocity of 100mm / s (10 times the minimum fluidizing velocity Umf), and the resin-coated magnetic particles were cooled for 80 minutes, and the temperature of the resin-coated magnetic particles was lowered to 70°C. Thereafter, the resin-coated magnetic particles were taken out of the fluidized bed apparatus and sieved with a mesh opening of 75μm to prepare carrier 1. The flow conditions and cooling conditions in the fluidized bed apparatus are summarized in Table 1.
[0182] [Table 1]
[0183] (Examples 2 to 15) Carriers 2 to 15 were prepared in the same manner as in Example 1, except that one or more of the crushing conditions of the resin-coated magnetic particles in step A, the flow conditions of the resin-coated magnetic particles in step B, and the cooling conditions in step C were changed as shown in Table 1 above.
[0184] Example 16 [Preparation of Mixture 2] Lacquer (a solution of 20 parts of polycyclohexyl methacrylate (weight average molecular weight: 50,000, glass transition temperature Tg: 100°C) mixed with 80 parts of toluene): 100 parts Carbon black (average particle size 0.2 μm): 0.2 parts The above materials were charged into a sand mill and dispersed for 30 minutes, and then mixed liquid 2 was obtained. A carrier 16 was produced using the mixed solution 2 in the same manner as in Example 1, except for the conditions shown in Table 1 above.
[0185] Comparative Example 1 Ferrite core (volume average particle size 35 μm): 100 parts Mixture 1: Amount that gives a resin solid content of 3.0 parts per 100 parts of ferrite core The above components were put into a batch-type stirring vacuum mixer (Inoue Manufacturing Co., Ltd. 50L kneader, stirring blade diameter D = 0.25m, clearance between the blade outer circumference and the casing inner wall / D = 3.5%) with the jacket temperature warmed to 90 ° C., and preheated (heated) to 70 ° C. while stirring and mixing at 60 rpm. Next, the internal pressure of the mixer was reduced to 5 kPa-abs, and this was continued until the load power value of the stirring blade before drying of the solvent increased as the drying progressed, and the drying was completed and the load power value decreased to 1.3 times or less of the value before drying, forming a resin coating layer on the surface of the magnetic particles to obtain resin-coated magnetic particles. At this time, the temperature of the obtained resin-coated magnetic particles had risen to 98 ° C. Next, the jacket temperature of the mixer was cooled to 20 ° C., and the temperature of the resin-coated magnetic particles was cooled to 70 ° C. while crushing the resin-coated magnetic particles over 90 minutes. Thereafter, the resin-coated magnetic particles were taken out of the mixer and sieved through a sieve with mesh openings of 75 μm to prepare carrier C1. The disintegration conditions in the mixer are summarized in Table 1.
[0186] Comparative Example 2 Carrier C2 was prepared in the same manner as in Example 1, except that in step B, the resin-coated magnetic particles were allowed to flow for 60 minutes while maintained at 85°C, and then in step C, the resin-coated magnetic particles were cooled for 60 minutes to lower the temperature of the resin-coated magnetic particles to 60°C.
[0187] Comparative Example 3 Carrier C3 was prepared in the same manner as in Example 1, except that in step B, the resin-coated magnetic particles were flowed for 60 minutes while maintained at 165°C, and then in step C, the resin-coated magnetic particles were cooled for 120 minutes to lower the temperature of the resin-coated magnetic particles to 70°C.
[0188] <Preparation of developer> Either one of carriers 1 to 16 or C1 to C3 and yellow toner (Y1) were placed in a V blender in a mixing ratio of carrier:toner=100:10 (mass ratio) and stirred for 20 minutes to obtain developers 1 to 16 or C1 to C3, respectively.
[0189] <Various measurements and evaluations> -Measurement of the coverage rate of the resin coating layer on the carrier- The coverage of the resin coating layer on the surface of the carrier was determined by X-ray photoelectron spectroscopy (XPS) according to the following method. The target carrier and magnetic particles with the resin coating layer removed from the target carrier were prepared. The resin coating layer was removed from the carrier by dissolving the resin component with toluene. The carrier and the magnetic particles with the resin coating layer removed were used as measurement samples, and Fe, C, O (atomic%) were quantified using XPS. The exposed ratio (%) of the magnetic particles was calculated by (Fe of the carrier) ÷ (Fe of the magnetic particles) × 100, and the coverage rate (%) of the resin coating layer was determined as (100 - exposed ratio of the magnetic particles).
[0190] -Measurement of the amount of free resin in the carrier- A certain amount of the carrier was weighed out, dispersed in water, and the dispersion was filtered while the carrier was fixed with a magnet. The filter paper was dried, and the amount of free resin was calculated from the difference in mass before and after the filter paper and the weighed amount of the carrier.
[0191] -Measurement of the percentage of aggregates in the carrier after 75μm sieve- The carrier was sieved using a sieve with 75 μm openings, and the sieved carrier was spread out so as not to overlap as much as possible. Scanning electron microscope (SEM) photographs were taken at 350x magnification, and the ratio of the number of carrier particles that had not been broken down into primary particles to the number of carrier particles in one field of view was measured.
[0192] -Evaluation of color dullness suppression- The evaluation of color dullness was carried out as follows. Using the 700 Digital Color Press (manufactured by Fujifilm Business Innovation Co., Ltd.) filled with the obtained developer, one 5 cm x 5 cm solid image patch was output (Sample 1), and after outputting 100,000 images with an area coverage of 5%, another 5 cm x 5 cm solid image patch was output (Sample 2). Then, the color gamuts (L *, a * , b * The color gamut was measured using an image densitometer X-RITE938 (manufactured by X-RITE). From the difference between the color gamut of Sample 2 and the color gamut of Sample 1, ΔE was calculated using the following formula, and this was used as an index for evaluating color dullness. ΔE = [(ΔL * ) 2 +(Δa * ) 2 +(Δb * ) 2 〕 1 / 2 Here, ΔL * = (Sample 2 L * -L of sample 1 * ), Δa * = (a of sample 2 * -Sample 1 a * ), Δb * = (b of sample 2 * - Sample 1 b * ). The evaluation criteria are as follows: -Evaluation criteria- G1: ΔE≦1.0 G2: 1.0<ΔE≦2.0 G3: 2.0<ΔE≦3.0 G4: 3.0<ΔE≦5.0 G5: 5.0<ΔE≦7.0 G6: 7.0<ΔE≦10.0 G7: 10.0<ΔE
[0193] The results of the measurements and evaluations are shown in Table 2.
[0194] [Table 2]
[0195] From the above results, it is apparent that the present embodiment is superior in suppressing dullness of the obtained image as compared with the comparative example.
[0196] Preferred aspects of the present disclosure are described below. (((1))) In a mixer, a mixed liquid containing a resin having a glass transition temperature Tg and a solvent is mixed with magnetic particles, and the mixture is heated to evaporate the solvent to form a resin coating layer on the surface of the magnetic particles to obtain resin-coated magnetic particles. The resin-coated magnetic particles are then heated to a temperature T A A step A of disintegrating the mixture while maintaining the temperature at 100° C.; In a fluidized bed device, the resin-coated magnetic particles after step A are heated to a temperature T B A step B of flowing the mixture while maintaining the temperature at A step C of cooling the resin-coated magnetic particles after the step B; having The temperature T A and the temperature T B and each of said carriers independently satisfies the glass transition temperature Tg-20°C or higher and the glass transition temperature Tg+50°C or lower.
[0197] (((2))) In the step A, the resin-coated magnetic particles are mixed at a temperature T A The method for producing an electrostatic image developing carrier according to (((1))), wherein the stirring conditions in the mixer when disintegrating the toner particles while maintaining the above constant satisfy the following formula 1 and formula 2: 0.2≦the peripheral speed of the stirring blade πDN (m / s)≦2.0 Formula 1 5×10 2 ≦ Mixing work load (peripheral speed πDN × mixing time T) ≦ 1.5 × 10 3 formula 2 In Equation 1 and Equation 2, D represents the diameter (m) of the stirring blade, N represents the rotation speed (rps) of the stirring blade, and T represents the time (s) from the point at which the load power value of the stirring blade before drying of the solvent increases as the drying progresses and the load power value falls to 1.3 times or less the value before drying when the drying is completed, to the point at which stirring in the mixer is completed. (((3))) The method for producing a carrier for developing an electrostatic image according to (((2))), wherein the condition of the above formula 2 is the condition of the following formula 2': 7×10 2≦ Mixing work load (peripheral speed πDN × mixing time T) ≦ 1 × 10 3 formula 2' In equation 2', D represents the diameter (m) of the agitator blade, N represents the rotation speed (rps) of the agitator blade, and T represents the time (s) from the point at which the load power value of the agitator blade before drying of the solvent increases as the drying progresses and the load power value falls to 1.3 times or less the value before drying when drying is completed, to the point at which mixing in the mixer is terminated.
[0198] (((4))) In the step B, the resin-coated magnetic particles after the step A are heated to a temperature T B The resin-coated magnetic particles are allowed to flow for 30 minutes or more while maintaining the temperature T C and cooling the resulting mixture to a glass transition temperature Tg-40° C. or lower. (((5))) In the step B, the resin-coated magnetic particles after the step A are heated to a temperature T B The superficial velocity V of the fluidizing gas in the fluidized bed apparatus when the fluidizing gas is fluidized in a state maintained at H The method for producing a carrier for developing an electrostatic image according to any one of (((1))) to (((4))), wherein (m / s) is from 1 to 5 times the minimum fluidization velocity Umf. (((6))) The superficial velocity V of the fluidizing gas in the fluidized bed apparatus H is from 2 to 3 times the minimum fluidization velocity Umf. (((7))) A method for producing an electrostatic image developer, comprising the method for producing an electrostatic image developing carrier according to any one of (((1))) to (((6))).
[0199] According to the invention related to (((1))), a mixture containing a resin having a glass transition temperature Tg and a solvent is mixed with magnetic particles in a mixer, the mixture is heated to evaporate the solvent, a resin coating layer is formed on the surface of the magnetic particles, and resin-coated magnetic particles are obtained. Then, the resin-coated magnetic particles are heated to a temperature T Aand a fluidized bed device for heating the resin-coated magnetic particles after step A to a temperature T B and cooling the resin-coated magnetic particles after step B. A is lower than the glass transition temperature Tg-20°C and step B is not performed, or B is less than the glass transition temperature Tg-20°C or more than the glass transition temperature Tg+50°C, the resulting image is better inhibited from becoming dull. According to the invention related to (((2))), in step A, the resin-coated magnetic particles are heated to a temperature T A The present invention provides a method for producing a carrier for developing electrostatic images, which is superior in suppressing color dullness in the obtained image compared to a case in which the stirring conditions in a mixer when disintegrating the toner particles while maintaining the above condition do not satisfy the condition of formula 2. According to the invention related to (((3))), in step A, the resin-coated magnetic particles are heated to a temperature T A The present invention provides a method for producing a carrier for developing electrostatic images, which is superior in suppressing color dullness in the obtained image compared to a case in which the stirring conditions in a mixer when disintegrating the toner particles while maintaining the above formula 2 satisfy the condition of formula 2 but do not satisfy the condition of formula 2'.
[0200] According to the invention related to (((4))), the resin-coated magnetic particles after step A are heated to a temperature T B After flowing the resin-coated magnetic particles for less than 30 minutes in a state maintained at 100° C., the resin-coated magnetic particles are cooled to a glass transition temperature Tg−40° C. or lower, or the resin-coated magnetic particles after step A are cooled to a temperature T B The present invention provides a method for producing a carrier for developing electrostatic images, which is superior in suppressing color dullness in the resulting image, compared to a method in which the resin-coated magnetic particles are flowed at a temperature maintained at 40° C. for 30 minutes or more and then cooled to a temperature lower than the glass transition temperature (Tg-40° C.). According to the invention related to (((5))), in step B, the resin-coated magnetic particles after step A are heated to a temperature T B The superficial velocity V of the fluidizing gas in the fluidized bed equipment when fluidizing the gas while maintaining the fluidization HThe present invention provides a method for producing a carrier for developing electrostatic images, which is more excellent in suppressing color dullness in the resulting image than when the minimum fluidization velocity Umf (m / s) is more than 5 times the minimum fluidization velocity Umf. According to the invention related to (((6))), in step B, the resin-coated magnetic particles after step A are heated to a temperature T B The superficial velocity V of the fluidizing gas in the fluidized bed equipment when fluidizing the gas while maintaining the fluidization H The present invention provides a method for producing a carrier for developing electrostatic images, which is superior in suppressing color dullness in the obtained image, as compared with a case in which the minimum fluidization velocity Umf (m / s) is more than 3 times and not more than 5 times the minimum fluidization velocity Umf. According to the invention related to (((7))), a mixture containing a resin having a glass transition temperature Tg and a solvent is mixed with magnetic particles in a mixer, the mixture is heated to evaporate the solvent, a resin coating layer is formed on the surface of the magnetic particles, and resin-coated magnetic particles are obtained. Then, the resin-coated magnetic particles are heated to a temperature T A and a fluidized bed device for heating the resin-coated magnetic particles after step A to a temperature T B and a step C of cooling the resin-coated magnetic particles after step B. A is lower than the glass transition temperature Tg-20°C and step B is not performed, or B The present invention provides a method for producing an electrostatic image developer, which is superior in suppressing color dullness in the obtained image, as compared with a method for producing an electrostatic image developing carrier having a glass transition temperature (Tg) of less than Tg-20°C or more than Tg+50°C. [Explanation of symbols]
[0201] 1Y, 1M, 1C, 1K Photoconductor (an example of an image carrier) 2Y, 2M, 2C, 2K Charging roll (an example of a charging means) 3 Exposure device (an example of an electrostatic image forming means) 3Y, 3M, 3C, 3K laser beam 4Y, 4M, 4C, 4K developing device (an example of developing means) 5Y, 5M, 5C, 5K Primary transfer roll (an example of a primary transfer means) 6Y, 6M, 6C, 6K Photoconductor cleaning device (an example of a cleaning means) 8Y, 8M, 8C, 8K toner cartridges 10Y, 10M, 10C, 10K Image forming units 20 Intermediate transfer belt (an example of an intermediate transfer body) 22 Driving Roll 24 Support roll 26 Secondary transfer roll (an example of a secondary transfer means) 28 Fixing device (an example of fixing means) 30 Intermediate transfer body cleaning device P Recording paper (an example of a recording medium) 107 Photoconductor (an example of an image carrier) 108 Charging roll (an example of charging means) 109 Exposure device (an example of electrostatic image forming means) 111 Developing device (an example of developing means) 112 Transfer device (an example of a transfer means) 113 Photoconductor cleaning device (an example of a cleaning means) 115 Fixing device (an example of fixing means) 116 Mounting Rail 117 Cabinet 118 Exposure Aperture 200 Process Cartridge 300 Recording paper (an example of a recording medium)
Claims
1. In a mixer, a mixture containing a resin having a glass transition temperature Tg and a solvent is mixed with magnetic particles, and the mixture is heated to evaporate the solvent to form a resin coating layer on the surface of the magnetic particles to obtain resin-coated magnetic particles. The resin-coated magnetic particles are then heated to a temperature T A A step A of disintegrating the mixture while maintaining the temperature at 100° C.; In a fluidized bed device, the resin-coated magnetic particles after step A are heated to a temperature T B A step B of flowing the mixture while maintaining the temperature at a step C of cooling the resin-coated magnetic particles after the step B; having The temperature T A and the temperature T B each of which independently satisfies the glass transition temperature Tg-20° C. or higher and the glass transition temperature Tg+50° C. or lower.
2. In the step A, the resin-coated magnetic particles are mixed at a temperature T A 2. The method for producing a carrier for developing an electrostatic image according to claim 1, wherein the stirring conditions in the mixer when disintegrating the toner particles while maintaining the above constant satisfy the conditions of the following formulas 1 and 2: 0.2≦the peripheral speed of the stirring blade πDN (m / s)≦2.0 Formula 1 5×10 2 ≦Mixing work load (peripheral speed πDN×mixing time T)≦1.5×10 3 Formula 2 In Equation 1 and Equation 2, D represents the diameter (m) of the stirring blade, N represents the rotation speed (rps) of the stirring blade, and T represents the time (s) from the point at which the load power value of the stirring blade before drying of the solvent increases as the drying progresses and the load power value falls to 1.3 times or less the value before drying when the drying is completed, to the point at which stirring in the mixer is completed.
3. The method for producing a carrier for developing an electrostatic image according to claim 2, wherein the condition of the formula 2 is the condition of the following formula 2': 7 x 10 2 ≦Mixing work load (peripheral speed πDN×mixing time T)≦1×10 3 Formula 2' In formula 2', D represents the diameter (m) of the agitator blade, N represents the rotation speed (rps) of the agitator blade, and T represents the time (s) from the point at which the load power value of the agitator blade before drying of the solvent increases as the drying progresses and the load power value falls to 1.3 times or less the value before drying when drying is completed, to the point at which mixing in the mixer is terminated.
4. In the step B, the resin-coated magnetic particles after the step A are heated to a temperature T B The resin-coated magnetic particles are allowed to flow for 30 minutes or more while maintaining the temperature T C 2. The method for producing a carrier for developing an electrostatic image according to claim 1, wherein the carrier is cooled to a glass transition temperature (Tg)-40° C. or lower.
5. In the step B, the resin-coated magnetic particles after the step A are heated to a temperature T B The superficial velocity V of the fluidizing gas in the fluidized bed apparatus when the fluidizing gas is fluidized in a state maintained at H 2. The method for producing a carrier for developing an electrostatic image according to claim 1, wherein (m / s) satisfies 1 to 5 times the minimum fluidization velocity Umf.
6. The superficial velocity V of the fluidizing gas in the fluidized bed apparatus H The method for producing a carrier for developing an electrostatic image according to claim 5 , wherein the minimum fluidization velocity Umf is from 2 to 3 times the minimum fluidization velocity Umf.
7. A method for producing an electrostatic image developer, comprising the method for producing the electrostatic image developing carrier according to any one of claims 1 to 6.
Citation Information
Patent Citations
JP147738A
Production of electrophotographic carrier
JP1996234499A